Insulating material

By adding a specific non-polymer dispersant to the insulating layer of the insulating material and controlling the specific surface area of ​​the silica particles, the problem of rising viscosity of the hydrophilic vapor phase silica mixed liquid is solved, and excellent performance of thermal insulation and productivity is achieved.

CN119654515AInactive Publication Date: 2025-03-18NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380057874.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-19
Filing Date
2023-08-14
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When using hydrophilic vapor phase silica in the existing thermal insulation materials, the viscosity of the mixed liquid is prone to increase, resulting in increased production difficulty and damage to inorganic fibers. It is difficult to properly maintain the viscosity by simply mixing dispersants, thereby affecting the thermal insulation.

Method used

By adding a specific non-polymer dispersant to the insulating layer of the insulating material, and controlling the BET specific surface area of ​​the silica particles to be above 90m2/g and less than 380m2/g, in order to suppress the increase in the viscosity of the mixed liquid, improve productivity, and maintain thermal insulation.

Benefits of technology

Excellent performance of thermal insulation and productivity is achieved, production problems caused by rising viscosity of the mixed liquid are avoided, and high mechanical strength and good thermal insulation properties of the thermal insulation material are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654515A_ABST
    Figure CN119654515A_ABST
Patent Text Reader

Abstract

Provided is a heat insulating material including a heat insulating layer. The heat insulating layer contains silica particles, inorganic fibers, and at least one type of non-polymer dispersant represented by formula (A1), (A2), (A3), or (A4). The silica particles have a BET specific surface area of 90 m2 / g or more and less than 380 m2 / g. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermal insulation material, and more specifically, to a thermal insulation material including a thermal insulation material layer containing a specific non-polymer dispersant. This application claims priority based on Japanese Patent Application No. 2022-131070 filed on August 19, 2022, the entire contents of which are incorporated herein by reference. Background Art

[0002] Non-aqueous electrolyte secondary batteries such as lithium-ion batteries are widely used as power sources for electric vehicles such as hybrid vehicles and electric vehicles, portable electronic devices such as portable terminals, portable phones, and notebook personal computers, wearable devices, etc. For example, in lithium-ion battery modules and lithium-ion battery packs mounted on electric vehicles, since a plurality of cells are stacked, sometimes adjacent cells are not directly in contact with each other, and a heat insulating material for heat insulation between cells is further arranged between the cells.

[0003] Patent document 1 describes an insulating sheet sandwiched between single cells in a battery pack, which is manufactured by a wet papermaking method by combining first particles composed of silica particles, second particles formed of titanium dioxide, etc., and linear or needle-shaped inorganic fibers, and describes that the sheet exhibits excellent insulating properties even in high temperature regions above 500°C.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-34278 Summary of the invention

[0007] Problems to be solved by the invention

[0008] The inventors of the present invention have found that a thermal insulation material containing inorganic fibers in addition to silica particles has high thermal insulation and excellent mechanical strength. The inventors of the present invention have clarified that such a thermal insulation material can be manufactured by mixing silica particles and inorganic fibers in a solvent, coating, and molding, but for example, when using hydrophilic fumed silica, the viscosity of the mixed solution tends to increase, and it becomes difficult to mix due to the increase in viscosity, and the productivity is significantly deteriorated. In particular, in the case of a thermal insulation material containing inorganic fibers, the increase in the viscosity of the mixed solution can also cause damage to the inorganic fibers, etc., so special attention is required. In view of the problem of increased viscosity of such a mixed solution, a mixed dispersant is also considered, but the inventors of the present invention have also clarified that when using hydrophilic fumed silica with a high specific surface area and making a mixed solution with a higher concentration containing inorganic fibers, the following new technical problems will arise: it is difficult to properly maintain the viscosity by simply mixing a dispersant, and the thermal insulation of the thermal insulation material is deteriorated.

[0009] An object of one aspect of the present invention is to provide a thermal insulation material having excellent thermal insulation properties and productivity.

[0010] Solutions for solving problems

[0011] According to the present specification, a thermal insulation material is provided, which includes a thermal insulation layer, wherein the thermal insulation layer contains silica particles, inorganic fibers, and at least one of the non-polymeric dispersants represented by the following formula (A1), (A2), (A3) or (A4). The BET specific surface area of ​​the silica particles is 90 m 2 / g or more and less than 380m 2 / g.

[0012]

[0013] (In formulas (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a heteroatom. 1 , R 2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 1 , R 2 , R 3 and R 4 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 5 represents a hydrocarbon group optionally containing a heteroatom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a heteroatom or a hydrogen atom.5 , R 6 and R 7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 5 , R 6 and R 7 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 8 and R 9 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

[0014] According to the heat insulating material of this structure, the heat insulating layer contains a specific non-polymer dispersant in addition to the silica particles and the inorganic fibers, thereby effectively suppressing the increase in viscosity of the mixed liquid thereof and improving productivity. In addition, by making the BET specific surface area of ​​the silica particles at 90 m 2 / g or more and less than 380m 2 / g, it is easy to appropriately achieve both suppression of viscosity increase of the mixed liquid and thermal insulation properties. Therefore, according to one aspect of the present invention, a thermal insulation material having excellent thermal insulation properties and productivity can be provided.

[0015] In some preferred embodiments, the content of the non-polymeric dispersant in the thermal insulation layer is 0.01% to 5% by mass, thereby better suppressing a decrease in thermal insulation properties and suppressing an increase in the viscosity of the mixed liquid.

[0016] In some aspects, as the silica particles, for example, at least one selected from the group consisting of dry silica, wet silica, and silica aerogel can be used.

[0017] In some embodiments, as the silica particles, at least one selected from the group consisting of hydrophilic fumed silica and hydrophobic fumed silica can be preferably used, and hydrophilic fumed silica is more preferred.

[0018] In some embodiments, the average primary particle size of the silica particles is preferably 100 nm or less. When the average primary particle size of the silica particles is less than the above value, it is easy to ensure good thermal insulation properties.

[0019] In some aspects, as the inorganic fiber, at least one selected from the group consisting of heat-resistant glass fiber and biosoluble inorganic fiber can be preferably used. Among them, glass fiber is preferred.

[0020] In some embodiments, the density of the thermal insulation layer is preferably 0.2 g / cm 3 ~0.5g / cm 3 When the density of the heat insulating layer is within the above range, it is easy to ensure good heat insulating properties and mechanical strength.

[0021] In some preferred embodiments, the thermal conductivity of the thermal insulating layer under the conditions of 80° C. and 2 MPa pressure is 0.045 W / (m·K) or less. From the viewpoint of realizing a thermal insulating material having good thermal insulation properties, it is advantageous to have such a thermal insulating layer.

[0022] In some preferred embodiments, the thermal conductivity of the thermal insulation layer under 600°C and 2 MPa pressure conditions is 0.08 W / (m·K) or less. From the perspective of achieving a thermal insulation material that exhibits good thermal insulation properties even under high temperature conditions, having such a thermal insulation layer is advantageous.

[0023] The thermal insulation material of some schemes further includes a coating layer composed of a resin film, and the thermal insulation material is stacked with the thermal insulation layer and the coating layer. The above-mentioned coating layer can help to suppress the falling of silica particles and the like of the thermal insulation layer and protect the thermal insulation layer. As an example of a scheme of the thermal insulation material including a coating layer, the following scheme can be listed: the thermal insulation material is stacked with two or more layers of the coating layer, and the two or more layers of the coating layer clamp and enclose the thermal insulation layer from the thickness direction, and seal the gap between the coating layers. The coating layer may have a vent that connects the gap to the external space.

[0024] The heat insulating material disclosed herein can be preferably used, for example, when arranged between cells of a battery module, by making use of its high heat insulating properties and excellent mechanical strength.

[0025] In addition, according to the present specification, there is provided a method for producing a thermal insulation material, comprising: a mixing step of mixing silica particles, inorganic fibers, and a non-polymeric dispersant represented by the following formula (A1), (A2), (A3), or (A4) in a solvent to obtain a mixed solution; a coating step of coating the mixed solution obtained in the mixing step to obtain a coating film; and a molding step of molding the coating film obtained in the coating step to obtain a thermal insulation layer. The above-mentioned manufacturing method can be preferably used for the manufacture of any thermal insulation material disclosed herein.

[0026]

[0027] (In formulas (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a heteroatom. 1 , R2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 1 , R 2 , R 3 and R 4 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 5 represents a hydrocarbon group optionally containing a heteroatom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a heteroatom or a hydrogen atom. 5 , R 6 and R 7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 5 , R 6 and R 7 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 8 and R 9 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

[0028] In some embodiments, the amount of the non-polymeric dispersant added to the mixed solution is preferably 0.05 to 5 parts by mass relative to 100 parts by mass of the silica particles. If the amount of the non-polymeric dispersant is within the above range, the mixed solution is dispersed stably and the thermal insulation of the thermal insulation material is good.

[0029] In some embodiments, the solvent is a protic solvent. In embodiments using a protic solvent, the effect brought about by applying the production method disclosed herein tends to be more effectively exerted.

[0030] In some embodiments, the surface tension of the solvent is less than 73 mN / m. If the surface tension of the solvent is within the above range, thermal insulation and mechanical strength are good. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a perspective view schematically showing an example of a battery module in which a heat insulating material according to an embodiment is arranged between single cells.

[0032] Figure 2 yes Figure 1 Sectional view along line II-II.

[0033] Figure 3 It is a perspective view schematically showing a heat insulating material according to one embodiment.

[0034] Figure 4 yes Figure 3 IV-IV line cross-sectional view.

[0035] Figure 5 It is a cross-sectional view schematically showing a heat insulating material according to another embodiment.

[0036] Figure 6 It is a cross-sectional view schematically showing a heat insulating material according to another embodiment.

[0037] Figure 7 It is a cross-sectional view schematically showing a heat insulating material according to another embodiment. DETAILED DESCRIPTION

[0038] The preferred embodiments of the present invention are described below. It should be noted that those skilled in the art can understand matters necessary for the implementation of the present invention other than matters specifically mentioned in this specification based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the field. In addition, in the following drawings, components and parts that play the same role are sometimes marked with the same figure marks for description, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments recorded in the drawings are schematic for the purpose of clearly illustrating the present invention, and may not accurately represent the size and scale of the products actually provided.

[0039] The inventors have found that the thermal insulation material containing inorganic fibers in addition to silica particles has high thermal insulation and excellent mechanical strength. Such thermal insulation materials can be manufactured by mixing silica particles and inorganic fibers in a solvent, coating and molding. For example, when using hydrophilic fumed silica and mixing with a protic solvent, the hydrophilic fumed silica and the protic solvent are hydrogen bonded, so the viscosity of the mixed solution is particularly easy to rise. If the viscosity is extremely high, mixing itself becomes difficult, and productivity is significantly deteriorated. Especially in the case of a thermal insulation material containing inorganic fibers, the increase in the viscosity of the mixed solution can also cause the breakage of the inorganic fibers, so it is necessary to pay special attention. For the problem of the increase in the viscosity of such a mixed solution, a mixed dispersant is also considered, but the inventors have clearly defined that in the case of using a hydrophilic fumed silica with a higher specific surface area, the following new technical problems will be generated: it is particularly difficult to suppress the increase in viscosity, and then if a large amount of dispersants are simply mixed in order to suppress the increase in viscosity, the thermal insulation of the obtained thermal insulation material will deteriorate. Furthermore, in the case of a mixed solution containing inorganic fibers at a relatively high concentration, it becomes more difficult to deal with the problem of increased viscosity.

[0040] The present inventors have found that by mixing a specific non-polymer dispersant, i.e., a "non-polymer dispersant represented by formula (A1), (A2), (A3) or (A4)," into the mixed liquid, the viscosity increase can be effectively suppressed to maintain productivity, and it is also very effective in solving the problem of reduced thermal insulation of the thermal insulation material. Furthermore, the present inventors have found that by adding the non-polymer dispersant, even if the density of the obtained thermal insulation material is not increased, the strain when compressed at a certain pressure is reduced. This will bring about the effect of reducing costs and improve the cost performance of the thermal insulation material.

[0041] The following describes in detail the "silica particles", "inorganic fibers", "non-polymer dispersants represented by formula (A1), (A2), (A3) or (A4) (hereinafter sometimes referred to as "non-polymer dispersants")" and the like contained in the thermal insulation layer.

[0042] Silica (silica, SiO2) can be classified into crystalline silica, amorphous silica, etc. according to structural characteristics, and can be classified into natural silica, synthetic silica, etc. according to the method of obtaining. In addition, among synthetic silica, it can be classified into dry silica, wet silica, silica aerogel, etc. according to the manufacturing method, and further among dry silica, it can be classified into silica obtained by combustion method, silica obtained by arc method, etc., and among wet silica, it can be classified into silica obtained by gel method, silica obtained by sedimentation method, etc. The type of silica particles in the present invention is not particularly limited, preferably dry silica, silica aerogel, and as a kind of dry silica, more preferably fumed silica, and among fumed silica, hydrophilic fumed silica is particularly preferred. It should be noted that hydrophilic fumed silica refers to fumed silica having mainly hydrophilic silanol groups (Si-OH) on the surface, and generally refers to fumed silica in which the silanol groups are not replaced by hydrophobic groups due to surface treatment, etc. It should be noted that silica particles generally exist in the form of aggregates formed by agglomeration of primary particles, or aggregates further agglomerate to exist in the form of agglomerated particles. The silica particles in the thermal insulation layer can be dispersed in the form of primary particles, in the form of aggregates, in the form of agglomerated particles, or in the form of a combination thereof.

[0043] The average primary particle size of the silica particles is not particularly limited, and is usually 1nm to 100nm, preferably 2nm or more, more preferably 4nm or more, preferably 80nm or less, more preferably 40nm or less, further preferably 30nm or less, and particularly preferably 20nm or less. The average primary particle size when the silica particles are fumed silica is usually 1nm to 40nm, preferably 2nm or more, more preferably 4nm or more, preferably 30nm or less, more preferably 20nm or less, and further preferably 18nm or less. The average primary particle size when the silica particles are silica aerogels is usually 1nm to 20nm, preferably 18nm or less, and more preferably 10nm or less. If the average primary particle size of the silica particles is within the range, it is easy to ensure good thermal insulation. It should be noted that as a method for grasping the average primary particle size of the silica particles, a method for measuring using an electron microscope such as a scanning electron microscope (SEM) and a transmission electron microscope (TEM) can be cited. Specifically, a method of randomly selecting silica particles reflected in an electron microscope and measuring the particle size and calculating the average value of the numerical value can be cited. The particle size may be a diameter of a spherical particle, a midpoint between a short axis and a long axis of an elliptical particle, or a midpoint between a short side and a long side of an irregular particle.

[0044] The average particle size of the secondary agglomerates (agglomerates of primary particles) of the silica particles is not particularly limited, and is generally 0.1 μm to 100 μm, preferably 1 μm or more, more preferably 2 μm or more, preferably 90 μm or less, more preferably 80 μm or less. It should be noted that as a method for determining the average particle size of the secondary agglomerates of the silica particles, a method for measuring using the same method as the primary particle size can be cited.

[0045] The BET specific surface area of ​​silica particles is 90 m 2 / g or more and less than 380m 2 / g, preferably 130m 2 / g or more, more preferably 175m 2 / g or more, more preferably 200m 2 / g or more, preferably 350m 2 / g or less, more preferably 320m 2 / g or less, more preferably 300m 2 / g or less. If the BET specific surface area of ​​the silica particles is within the above range, it is also easy to ensure thermal insulation under high temperature and high humidity conditions. It should be noted that the BET specific surface area can be measured by a multi-point nitrogen adsorption method (BET method) according to the measurement method of ISO5794 / 1 of the International Organization for Standardization. In addition, for example, the nominal value of the BET specific surface area of ​​"AEROSIL380" manufactured by AEROSIL is 380m 2 / g, if the error is taken into account, it can be expressed as 350m 2 / g~410m 2 In this case, the nominal value, i.e., 380 m / s, is used in this specification. 2 / g is considered as the benchmark.

[0046] The apparent specific gravity of the silica particles is not particularly limited, and is generally 30 g / L to 130 g / L, preferably 40 g / L or more, more preferably 50 g / L or more, preferably 100 g / L or less, more preferably 80 g / L or less, and further preferably 60 g / L or less. It should be noted that the apparent specific gravity of the silica particles can be listed as the value obtained by filling the silica particles in a container capable of measuring the volume, such as a 250 mL graduated cylinder, measuring the filling mass (Xg) and the filling volume (YmL) of the silica particles, and dividing the filling mass by the filling volume ([apparent specific gravity (g / L)] = X / Y×1000).

[0047] Examples of the silica particles include AEROSIL 50, 90, 130, 200, 300, and 380 of the AEROSIL series (manufactured by AEROSIL Japan Co., Ltd.), QS-09, QS-10, QS-102, QS-20, QS-30, and QS-40 of the REOLOSIL series (manufactured by TOKUYAMA Co., Ltd.), and HDKV15, N20, T30, and T40 of the HDK series (manufactured by WACKER ASAHIKASEI SILICONE Co., Ltd.); AEROSIL R972 and R976S of the AEROSIL series (manufactured by AEROSIL Japan Co., Ltd.), and HDK series (manufactured by WACKER ASAHIKASEI SILICONE Co., Ltd.). HDKH15, H20, H30, etc. manufactured by SILICONE Co., Ltd.; airlica (manufactured by TOKUYAMA Co., Ltd.) as silica aerogel, etc. It should be noted that the heat insulating layer may contain one type of silica particles, or may contain two or more types of silica particles.

[0048] The content of the silica particles in the thermal insulation layer is not particularly limited, and is generally 50% to 99.5% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less. If the content of the silica particles is within the above range, it is easy to ensure good thermal insulation and mechanical strength.

[0049] The types of inorganic fibers are not particularly limited, and examples thereof include silica fibers, glass fibers, alumina fibers, silica-alumina fibers, silica-alumina-magnesia fibers, biosoluble inorganic fibers, glass fibers, zirconia fibers, alkaline earth metal silicate fibers, alkaline earth silicate (AES) fibers, glass wool, rock wool, and basalt fibers. If the inorganic fiber is the material, the heat resistance is improved. It should be noted that the thermal insulation layer may contain one inorganic fiber, or may contain two or more inorganic fibers.

[0050] The content of the inorganic fiber in the heat insulating layer is not particularly limited, and is generally 0.5% to 50% by mass, preferably 1% by mass or more, more preferably 3% by mass or more, further preferably 5% by mass or more, preferably 40% by mass or less, more preferably 35% by mass or less, further preferably 30% by mass or less. If the content of the fiber is within the above range, it is easy to ensure good thermal resistance and easy to manufacture the heat insulating layer.

[0051] The average fiber length of the inorganic fiber is not particularly limited, and is usually 0.05 mm to 50 mm, preferably 0.5 mm or more, more preferably 1.0 mm or more, further preferably 2 mm or more, preferably 25 mm or less, more preferably 13 mm or less, further preferably 10 mm or less, and may be 8 mm or less, and may be 6 mm or less. If the average fiber length of the fiber is within the above range, it is easy to manufacture the thermal insulation layer.

[0052] The average fiber diameter of the inorganic fiber is not particularly limited, and is generally 0.1 μm to 50 μm, preferably 1 μm or more, more preferably 5 μm or more, further preferably 7 μm or more, preferably 25 μm or less, more preferably 20 μm or less, further preferably 15 μm or less. If the average fiber diameter of the fiber is within the above range, it is easy to ensure good thermal insulation and mechanical strength.

[0053] The inorganic fibers preferably include inorganic fibers having a fiber length of 6 mm or more and less than 35 mm. The ratio of the number of inorganic fibers having a fiber length of 6 mm or more and less than 35 mm in the total inorganic fibers is not particularly limited, but is usually 30% to 100%, preferably 95% or less, preferably 35% or more, more preferably 40% or more, and further preferably 50% or more. If the content ratio of the fibers having the above fiber length is within the above range, it is easy to ensure good thermal insulation and mechanical strength.

[0054] The heat-insulating layer may also contain organic fibers in addition to inorganic fibers. Specific examples of organic fibers include cellulose fibers, felt formed by polyester, polypropylene, etc. The use of organic fibers may be advantageous from the viewpoints of improving cushioning properties and durability against repeated pressure fatigue. The content of organic fibers in the heat-insulating layer may be appropriately set in such a way as to obtain the desired effect of use, and may be, for example, more than 0 mass parts, more than 1 mass part, more than 4 mass parts, more than 8 mass parts, or more than 16 mass parts relative to 100 mass parts of inorganic fibers. On the other hand, in some schemes, from the viewpoint of heat resistance, etc., it is appropriate that the content of organic fibers in the heat-insulating layer is less than 100 mass parts relative to 100 mass parts of inorganic fibers, and it is advantageous to have less than 50 mass parts, and it may be less than 20 mass parts, less than 10 mass parts, less than 5 mass parts, or less than 1 mass part, and the heat-insulating layer may not contain organic fibers.

[0055] The non-polymer dispersant is a compound represented by the following formula (A1), (A2), (A3) or (A4).

[0056]

[0057] (In formulas (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a heteroatom. 1 , R 2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 1 , R 2 , R 3 and R 4 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 5 represents a hydrocarbon group optionally containing a heteroatom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a heteroatom or a hydrogen atom. 5 , R 6 and R7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 5 , R 6 and R 7 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 8 and R 9 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

[0058] Here, "non-polymer type" refers to a molecule that does not contain a polymer generated by a polymerization reaction, that is, a so-called "low molecular compound". Dispersants are sometimes classified into: 1) polymer dispersants, 2) surfactant dispersants (low molecular dispersants), 3) inorganic dispersants, etc. Non-polymer dispersants belong to "2) surfactant dispersants (low molecular dispersants)". In addition, as shown in formulas (A1), (A2), (A3) and (A4), non-polymer dispersants can be said to be cationic surfactants such as quaternary ammonium salts, amine salts, and pyridinium salts. It should be noted that the non-polymer dispersant in the thermal insulation layer can exist in the form of a salt combined with a counter ion, or in the form of a free compound or ion. Examples of the above salts include ammonium salts of the dispersant of formula (A1) and counter ions (such as chloride ions, bromide ions, ethyl sulfate ions, etc.), and amine salts of the dispersant of formula (A3) and acetic acid.

[0059] Hereinafter, formulas (A1) to (A4) will be described in detail.

[0060] R in formula (A1) and (A2) 1 , R 2 , R 3 and R 4 Each independently represents a "hydrocarbon group optionally containing a heteroatom". The above-mentioned hydrocarbon group may have not only a straight-chain structure but also a branched structure, a cyclic structure, a carbon-carbon unsaturated bond (carbon-carbon double bond, carbon-carbon triple bond), etc., and may be any of a saturated hydrocarbon group, an unsaturated hydrocarbon group, an alicyclic saturated hydrocarbon group, an alicyclic unsaturated hydrocarbon group, an aromatic hydrocarbon group, etc.

[0061] In addition, "a hydrocarbon group optionally containing a heteroatom" means that the carbon atoms and hydrogen atoms of the hydrocarbon group are optionally replaced by heteroatoms, or a functional group containing heteroatoms is optionally formed at the end or inside the hydrocarbon group. Specific examples of heteroatoms include nitrogen atoms (N), oxygen atoms (O) and sulfur atoms (S), and preferred examples include nitrogen atoms and oxygen atoms. For example, "a hydrocarbon group optionally containing a nitrogen atom" means that the carbon atoms and hydrogen atoms of the hydrocarbon group are optionally replaced by nitrogen atoms, and a functional group containing a nitrogen atom such as a primary amino group (-NH2), a secondary amino group (-NH-), a tertiary amino group (-N<), and an imino group (=N-) is formed at the end or inside the hydrocarbon group. In addition, "a hydrocarbon group optionally containing an oxygen atom" means that the carbon atoms and hydrogen atoms of the hydrocarbon group are optionally replaced by oxygen atoms, and a functional group containing an oxygen atom such as an ether bond (-O-), a carbonyl group (=O), and a hydroxyl group (-OH) is formed at the end or inside the hydrocarbon group. Furthermore, "a hydrocarbon group optionally containing a sulfur atom" means that carbon atoms or hydrogen atoms of the hydrocarbon group are optionally substituted with sulfur atoms to form a functional group containing a sulfur atom such as a thioether bond (-S-) or a thiol group (-SH) at the terminal or inside the hydrocarbon group.

[0062] In the case where the above hydrocarbon group contains heteroatoms, a hydrocarbon group (e.g. R in formula (A3) 5 ) may be one or more than two. Generally, it is appropriate that the number of heteroatoms contained in one hydrocarbon group is six or less, preferably five or less or four or less, more preferably three or less or two or less. In addition, the types of heteroatoms contained in one hydrocarbon group may be one or more than two.

[0063] Furthermore, R 1 , R 2 , R 3 and R 4 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. Examples of the group "bonded to each other to form a ring structure" include the cation in cetylpyridinium chloride represented by the following formula. Cetylpyridinium chloride can be considered to be a salt of a cation belonging to formula (A2) and a chloride ion. The cation in formula (A2) is 1 is hexadecyl, R 2 With R 3 The ring structure formed may have a carbon-carbon unsaturated bond. In cetylpyridinium chloride, the ring structure formed has a carbon-carbon unsaturated bond to form a pyridinium structure.

[0064]

[0065] R in formula (A1) and (A2) 1 , R 2 , R 3 and R 4The total number of carbon atoms obtained by combining the hydrocarbon groups (hereinafter, sometimes referred to as "total number of C") is 8 to 40 (e.g., 12 to 40). When considering the cation of the cetylpyridinium chloride, R 1 It is hexadecyl, so the number of carbon atoms is 16, R 2 With R 3 The number of carbon atoms is 5. Therefore, in the cation of hexadecylpyridinium chloride, R 1 , R 2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 16+5=21.

[0066] R in formula (A1) and (A2) 1 , R 2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40 (for example, 12 to 40). It is generally advantageous for the above-mentioned total number of carbon atoms to be 9 or more, and preferably 10 or more (for example, 11 or more or 12 or more). In some embodiments, the above-mentioned total number of carbon atoms is preferably 13 or more, more preferably 14 or more, further preferably 15 or more, preferably 35 or less, more preferably 25 or less, and further preferably 20 or less. If the total number of carbon atoms is within the above range, the dispersion of the compounding liquid can be stable, and the thermal insulation properties of the thermal insulation material are good. In some embodiments, it is appropriate for the above-mentioned total number of carbon atoms to be 18 or less, and it can be 16 or less, it can be 14 or less, it can be 13 or less, or 12 or less. From the perspective of the fluidity of the compounding liquid (for example, the improvement of fluidity brought about by the increase of cone penetration) within the range that can obtain appropriate dispersion stability, it may be advantageous that the above-mentioned total number of carbon atoms is not too much.

[0067] R in formula (A1) and (A2) 1 , R 2 , R 3 and R 4 The number of carbon atoms of at least one hydrocarbon group in the compound is usually 5 to 35 or 6 to 35 (e.g., 8 to 35). In some embodiments, the number of carbon atoms is preferably 10 or more, more preferably 11 or more, and further preferably 12 or more, preferably 30 or less, more preferably 20 or less, and further preferably 18 or less, and may be 16 or less, may be 14 or less, may be 12 or less, 10 or less, or 9 or less. If the number of carbon atoms is within the above range, the formulation is easily dispersed and stable.

[0068] R in formula (A3) 5 Represents a hydrocarbon group, R 6 and R 7Each independently represents a "hydrocarbon group optionally containing a heteroatom" or a "hydrogen atom." The hydrocarbon group has the same meaning as the hydrocarbon group in the above formula (A1) and formula (A2), and the hydrocarbon groups may also be bonded to each other to form a ring structure.

[0069] In formula (A3), R 5 , R 6 and R 7 The total number of carbon atoms (total C number) obtained by combining the hydrocarbon groups is 8 to 40 (for example, 12 to 40). It is generally advantageous for the total number of carbon atoms to be 9 or more, and preferably 10 or more (for example, 11 or more or 12 or more). In some embodiments, the total number of carbon atoms is preferably 13 or more, more preferably 14 or more, further preferably 15 or more, preferably 35 or less, more preferably 25 or less, and further preferably 20 or less. If the total number of carbon atoms is within the range, the dispersion of the compounding liquid can be stable, and the thermal insulation properties of the thermal insulation material are good. In some embodiments, it is appropriate for the total number of carbon atoms to be 18 or less, and it can be 16 or less, 14 or less, 13 or less, or 12 or less. From the perspective of the fluidity of the compounding liquid (for example, the improvement in fluidity due to the increase in cone penetration) within the range that can obtain appropriate dispersion stability, it may be advantageous that the total number of carbon atoms is not too much.

[0070] R in formula (A3) 5 , R 6 and R 7 The number of carbon atoms of at least one hydrocarbon group in the compound is usually 6 to 35 (e.g., 8 to 35), preferably 10 or more, more preferably 11 or more, further preferably 12 or more, preferably 30 or less, more preferably 20 or less, further preferably 18 or less. When the number of carbon atoms is within the above range, the formulation is easily dispersed and stable.

[0071] R in formula (A4) 8 and R 9 Each independently represents a "hydrocarbon group which may contain a hetero atom." The hydrocarbon group has the same meaning as the hydrocarbon group in the above formula (A1) and formula (A2), and the hydrocarbon groups may also be bonded to each other to form a ring structure.

[0072] R in formula (A4) 8 and R 9The total number of carbon atoms (total C number) obtained by combining the hydrocarbon groups is 8 to 40 (for example, 12 to 40). It is generally advantageous for the above-mentioned total number of carbon atoms to be 9 or more, and preferably 10 or more (for example, 11 or more or 12 or more). In some embodiments, the above-mentioned total number of carbon atoms is preferably 13 or more, more preferably 14 or more, further preferably 15 or more, preferably 35 or less, more preferably 25 or less, and further preferably 20 or less. If the total number of carbon atoms is within the above range, the dispersion of the compounding liquid can be stable, and the thermal insulation properties of the thermal insulation material are good. In some embodiments, it is appropriate for the above-mentioned total number of carbon atoms to be 18 or less, and it can be 16 or less, it can be 14 or less, it can be 13 or less, or it can be 12 or less. Within the range that can obtain appropriate dispersion stability, from the perspective of the fluidity of the compounding liquid (for example, the improvement of fluidity brought about by the increase of cone penetration), it may be advantageous that the above-mentioned total number of carbon atoms is not too much.

[0073] R in formula (A4) 8 and R 9 The number of carbon atoms of at least one hydrocarbon group in the compound is usually 7 to 35 (e.g., 8 to 35), preferably 10 or more, more preferably 11 or more, further preferably 12 or more, preferably 30 or less, more preferably 20 or less, further preferably 18 or less. When the number of carbon atoms is within the above range, the formulation is easily dispersed and stable.

[0074] Examples of the non-polymeric dispersant represented by the formula (A1) include the non-polymeric dispersants represented by the following (A1-1) or (A1-2).

[0075]

[0076] (R in formula (A1-1) 1 represents a hydrocarbon group having 5 to 37 (eg, 9 to 34) carbon atoms which may contain a heteroatom (eg, a nitrogen atom). 1 represents a hydrocarbon group having 2 to 34 (e.g., 9 to 34) carbon atoms which may contain a heteroatom (e.g., a nitrogen atom).

[0077] Examples of the salt of the non-polymeric dispersant represented by formula (A1) include nonyltrimethylammonium chloride (C9H 19 N + (CH3)3Cl), nonyltrimethylammonium bromide (C9H 19 N + (CH3)3Br), decyltrimethylammonium chloride (C 10 H 21 N + (CH3)3Cl), decyltrimethylammonium bromide (C 10 H 21 N +(CH3)3Br), undecyltrimethylammonium chloride (C 11 H 23 N + (CH3)3Cl), undecyltrimethylammonium bromide (C 11 H 23 N + (CH3)3Br), dodecyltrimethylammonium chloride (C 12 H 25 N + (CH3)3Cl), dodecyltrimethylammonium bromide (C 12 H 25 N + (CH3)3Br), tridecyltrimethylammonium chloride (C 13 H 27 N + (CH3)3Cl), tridecyltrimethylammonium bromide (C 13 H 27 N + (CH3)3Br), tetradecyltrimethylammonium chloride (C 14 H 29 N + (CH3)3Cl), tetradecyltrimethylammonium bromide (C 14 H 29 N + (CH3)3Br), pentadecyltrimethylammonium chloride (C 15 H 31 N + (CH3)3Cl), pentadecyltrimethylammonium bromide (C 15 H 31 N + (CH3)3Br), hexadecyltrimethylammonium chloride (C 16 H 33 N + (CH3)3Cl), hexadecyltrimethylammonium bromide (C 16 H 33 N + (CH3)3Br), heptadecyltrimethylammonium chloride (C 17 H 35 N + (CH3)3Cl), heptadecyltrimethylammonium bromide (C 17 H 35 N + (CH3)3Br), octadecyltrimethylammonium chloride (C 18 H 37 N + (CH3)3Cl), octadecyltrimethylammonium bromide (C 18 H 37 N+ (CH3)3Br), nonadecylammonium chloride (C 19 H 39 N + (CH3)3Cl), nonadecylammonium bromide (C 19 H 39 N + (CH3)3Br), eicosyltrimethylammonium chloride (C 20 H 41 N + (CH3)3Cl), eicosyltrimethylammonium bromide (C 20 H 41 N + (CH3)3Br), heneicosyltrimethylammonium chloride (C 21 H 43 N + (CH3)3Cl), heneicosyltrimethylammonium bromide (C 21 H 43 N + (CH3)3Br), behenyltrimethylammonium chloride (C 22 H 45 N + (CH3)3Cl), behenyltrimethylammonium bromide (C 22 H 45 N + (CH3)3Br), tris(C 23 H 47 N + (CH3)3Cl), tris(C 23 H 47 N + (CH3)3Br), tetradecyltrimethylammonium chloride (C 24 H 49 N + (CH3)3Cl), tetradecyltrimethylammonium bromide (C 24 H 49 N + (CH3)3Br), pentadecyltrimethylammonium chloride (C 25 H 51 N + (CH3)3Cl), dipentadecandimethylammonium bromide (C 25 H 51 N + (CH3)3Br), hexadecyltrimethylammonium chloride (C 26 H 53 N + (CH3)3Cl), hexadecyltrimethylammonium bromide (C 26H 53 N + (CH3)3Br), dioctyltrimethylammonium chloride (C 27 H 55 N + (CH3)3Cl), dioctyltrimethylammonium bromide (C 27 H 55 N + (CH3)3Br), dioctadecyl dimethyl ammonium chloride ((C 18 H 37 )2N + (CH3)2Cl), etc. Other examples of the salt of the non-polymeric dispersant represented by formula (A1) include amyltrimethylammonium chloride (total carbon number 8), amyltrimethylammonium bromide, hexyltrimethylammonium chloride (total carbon number 9), hexyltrimethylammonium bromide, heptyltrimethylammonium chloride (total carbon number 10), heptyltrimethylammonium bromide, octyltrimethylammonium chloride (total carbon number 11), octyltrimethylammonium bromide, dibutyldimethylammonium chloride (total carbon number 10), dibutyldimethylammonium bromide, dihexyldimethylammonium chloride (total carbon number 14), dihexyldimethylammonium bromide, dioctyldimethylammonium chloride (total carbon number 18), dioctyldimethylammonium bromide, didecyldimethylammonium chloride (total carbon number 22), didecyldimethylammonium bromide, octyldimethylethylammonium ethylsulfate (total carbon number 12), etc.

[0078] Examples of the non-polymer dispersant represented by the formula (A2) include the non-polymer dispersants represented by the following (A2-1).

[0079]

[0080] (In formula (A2-1), R 1 and R 10 Each independently represents a hydrocarbon group optionally containing a heteroatom (such as a nitrogen atom), i represents an integer from 0 to 5, and R 1 and R 10 The total number of carbon atoms obtained by combining the hydrocarbon groups is 3 to 35 (e.g., 7 to 35).

[0081] Examples of the salt of the non-polymeric dispersant represented by formula (A2) include: dodecylpyridinium chloride (C 12 H 25 N + C5H5Cl), dodecylpyridinium bromide (C 12 H 25 N + C5H5Br), cetylpyridinium chloride (C 16 H 33 N +C5H5Cl), cetylpyridinium bromide (C 16 H 33 N + C5H5Br), 1-hexadecyl-4-methylpyridinium chloride (C 16 H 33 N + C5H5(CH3)Cl) etc.

[0082] Examples of the non-polymer dispersant represented by formula (A3) include the non-polymer dispersants represented by the following (A3-1), (A3-2) or (A3-3).

[0083]

[0084] (In formula (A3-1), R 5 represents a hydrocarbon group optionally containing a heteroatom (eg, a nitrogen atom), R 5 The number of carbon atoms in the formula (A3-2) is 8 to 40 (e.g., 8 to 35). 5 represents a hydrocarbon group optionally containing a heteroatom (eg, a nitrogen atom), R 5 The number of carbon atoms in the formula (A3-3) is 6 to 38 (e.g., 7 to 35). 5 and R 11 Each independently represents a hydrocarbon group optionally containing a heteroatom (such as a nitrogen atom), j represents an integer from 0 to 5, and R 5 and R 11 The total number of carbon atoms obtained by combining the hydrocarbon groups is 3 to 35 (e.g., 7 to 35).

[0085] Examples of the non-polymeric dispersant represented by formula (A3) include: dodecylamine (C 12 H 25 NH2), dodecyl dimethyl amine (C 12 H 25 N(CH3)2), tridecylamine (C 13 H 27 NH2), tetradecylamine (C 14 H 29 NH2), pentadecylamine (C 15 H 31 NH2), hexadecylamine (C 16 H 33 NH2), hexadecyl dimethylamine (C 16 H 33 N(CH3)2), heptadecylamine (C 17 H 35 NH2), octadecylamine (C 18 H 37 NH2), nonadecylammonium amine (C19 H 39 NH2), eicosylamine (C 20 H 41 NH2), heneicosylamine (C 21 H 43 NH2), docosylamine (C 22 H 45 NH2), tris(C 23 H 47 NH2), tetradecylamine (C 24 H 49 NH2), pentadecylamine (C 25 H 51 NH2), hexadecylamine (C 26 H 53 NH2), heptadecylamine (C 27 H 55 NH2), N-dodecylpiperidine (C 12 H 25 NC5H 10 ) and the like. Other examples of the non-polymeric dispersant represented by formula (A3) include hexyldimethylamine, heptyldimethylamine, octylamine, octyldimethylamine, nonylamine, nonyldimethylamine, decylamine, decyldimethylamine, and undecylamine. Another example of the non-polymeric dispersant represented by formula (A3) includes R 5 , R 6 , R 7 A non-polymeric dispersant in which at least one of the dispersants is a hydrocarbon group containing a heteroatom (e.g., a hydrocarbon group having an ether bond and / or a hydroxyl group). A specific example of such a non-polymeric dispersant is stearyl propylene glycol dimethylamine (C 18 H 37 OCH2CH(OH)CH2N(CH3)2).

[0086] Examples of the non-polymer dispersant represented by the formula (A4) include the non-polymer dispersants represented by the following (A4-1).

[0087]

[0088] (In formula (A4-1), R 12 Each independently represents a hydrocarbon group optionally containing a heteroatom (such as a nitrogen atom), k represents an integer of 0 to 5 (typically 1 to 5), and R 12 The total number of carbon atoms obtained by combining the hydrocarbon groups is 3 to 35 (e.g., 7 to 35).

[0089] Examples of the non-polymeric dispersant represented by formula (A4) include 4-dodecylpyridine (C12 H 25 NC5H5), 2-methyl-4-tridecylpyridine (C 13 H 27 NC5H4(CH3))、2-Tetradecylpyridine(C 14 H 29 NC5H5), 4-pentadecylpyridine (C 15 H 31 NC5H5) etc.

[0090] As for the content of the non-polymeric dispersant in the thermal insulation layer, the non-polymeric dispersant is reduced compared to the compounding amount during the manufacturing process of the thermal insulation layer, so it can be considered as a residual amount. The content of the non-polymeric dispersant in the thermal insulation layer is not particularly limited. The content of the non-polymeric dispersant in the thermal insulation layer typically exceeds 0 mass %, for example, it can be more than 0.0001 mass %, it can be more than 0.0005 mass %, it can be more than 0.001 mass % or more than 0.05 mass %. In addition, the content of the non-polymeric dispersant in the thermal insulation layer can be, for example, less than 7 mass %, and from the viewpoint of easily avoiding the influence on other characteristics, it is usually appropriate to be less than 5 mass % (for example, more than 0.0001 mass % and less than 5 mass %). In some embodiments, the content of the non-polymeric dispersant in the heat-insulating layer is usually 0.01% to 5% by mass, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, further preferably 0.2% by mass or more, preferably 3% by mass or less, more preferably 2% by mass or less, further preferably 1% by mass or less, particularly preferably 0.5% by mass or less, and may be 0.3% by mass or less, 0.1% by mass or less, 0.05% by mass or less, 0.01% by mass or less, 0.005% by mass or less, 0.001% by mass or less, or 0.0005% by mass or less. The content of the non-polymeric dispersant in the heat-insulating layer can be obtained by extracting the non-polymeric dispersant from the heat-insulating layer using an appropriate solvent (a solvent that can dissolve the target non-polymeric dispersant) and performing quantitative analysis using a known method. The type of the non-polymer dispersant contained in the heat insulating layer can be determined by extracting the non-polymer dispersant from the heat insulating layer using an appropriate solvent as described above and identifying the non-polymer dispersant contained in the obtained extract using a known method.

[0091] As long as the insulating layer is the layer containing silica particles, inorganic fibers and non-polymeric dispersants, it may contain other components, specifically, inorganic particles other than silica particles (hereinafter sometimes referred to as "other inorganic particles") containing adhesives (binders) can be listed. The type of adhesive in the case where the insulating material contains an adhesive is not particularly limited, specifically, thermoplastic resins, thermosetting resins, sugars, etc. can be listed. The insulating layer may contain one adhesive, or may contain two or more adhesives. By containing the adhesive, the shape stability is improved.

[0092] When the heat insulating layer contains a binder, the type of binder is not particularly limited, and can be classified into organic binders and inorganic binders. Specific examples of organic binders include: thermoplastic resins, thermoplastic elastomers, thermosetting resins, thermosetting elastomers, sugars, water-soluble polymers, etc. Specific examples of inorganic binders include: aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide, calcium oxide, etc. If the binder is the above-mentioned binder, the shape stability is improved. It should be noted that the heat insulating layer may contain one binder, or may contain two or more binders.

[0093] The content of the adhesive in the case where the heat insulating layer contains an adhesive is not particularly limited, and is generally 0.01% to 10% by mass, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, further preferably 0.2% by mass or more, preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 1% by mass or less. If the content of the adhesive is within the range, the heat insulating layer easily takes into account both heat insulation and shape stability. If the content of the adhesive is within the range, it is easy to take into account both heat insulation and shape stability.

[0094] The types of other inorganic particles in the case where the thermal insulation layer contains other inorganic particles are not particularly limited, and examples thereof include: zinc oxide, aluminum oxide, titanium oxide, silicon carbide, ilmenite (ilmenite, FeTiO), zirconium silicate, iron (III) oxide, iron (II) (würzburgite (FeO), magnetite (Fe3O4), hematite (Fe2O3)), chromium dioxide, zirconium oxide, manganese dioxide, zirconium oxide sol, titanium dioxide sol, silica sol, alumina sol, bentonite and kaolin, etc. In addition, carbonaceous particles such as graphite, carbon black, and carbon powder can also be used as the above-mentioned inorganic particles in the technology disclosed herein. As graphite, graphite with a particle size of less than 18 μm is preferred. The particle size of graphite is measured in the same manner as the average primary particle size of silica particles. When a nominal value of the particle size is provided by a manufacturer, the nominal value can also be used. The shape of graphite can be any of flaky, scaly, spherical, etc. As commercial products of flaky graphite, for example, BF-3AK, FBF, BF-10AK, etc. manufactured by Chugoshi Graphite Industry Co., Ltd., GE-1, Z-5F, CNP7, V-10F, etc. manufactured by Ito Graphite Industry Co., Ltd. are listed. As commercial products of flaky graphite, HLP, SB-1, etc. manufactured by Chugoshi Graphite Industry Co., Ltd. are listed. As commercial products of spherical graphite, SG-BH8, etc. manufactured by Ito Graphite Industry Co., Ltd. are listed. As commercial products of carbon black, TOKABLACK#5500 manufactured by TOKAICARBON Co., Ltd., MA100 manufactured by Mitsubishi Chemical Co., Ltd. are listed. Although not particularly limited, in some schemes using carbon black as inorganic particles, as the above-mentioned carbon black, from the viewpoint of reducing thermal conductivity, it is generally preferred to use carbon black with a higher DBP oil absorption. The DBP oil absorption is, for example, 40 mL / 100 g or more, preferably 60 mL / 100 g or more or 80 mL / 100 g or more. The heat insulating layer may contain one inorganic particle, or may contain two or more inorganic particles. Inorganic particles that can suppress thermal radiation, more specifically, inorganic particles that have an absorption peak in the infrared region, are particularly preferred. The absorption peak in the infrared region can be measured using an infrared spectrophotometer. In addition, the inorganic particles may also function as a binder that bonds inorganic fibers to each other.

[0095] The heat insulating layer is the layer containing silica particles, inorganic fibers and non-polymeric dispersants, and is preferably a molded body obtained by molding a mixture containing silica particles, inorganic fibers and non-polymeric dispersants. When the heat insulating layer is a molded body obtained by molding a mixture containing silica particles, inorganic fibers and non-polymeric dispersants, the details of the mixing method of silica particles, inorganic fibers and non-polymeric dispersants will be described later.

[0096] The thickness of the heat-insulating layer is not particularly limited, and is usually 0.5 to 10 mm, preferably 0.7 mm or more, more preferably 0.8 mm or more or 0.9 mm or more. In some embodiments, the thickness of the heat-insulating layer is preferably 1 mm or more, more preferably 1.5 mm or more, further preferably 2 mm or more, preferably 7 mm or less, more preferably 5 mm or less, and further preferably 3 mm or less. If the thickness of the heat-insulating layer is within the range, it is easy to ensure good insulation and suppress the large-scale heat-insulating material. In addition, in some embodiments, the thickness of the heat-insulating layer can be less than 2 mm, less than 1.5 mm, less than 1.3 mm, less than 1 mm or less than 1 mm. By reducing the thickness of the heat-insulating layer, the heat-insulating material can be thinned and lightweight. It should be noted that, with respect to the thickness of the heat-insulating layer, the average value of the values ​​obtained by measuring the cross-section of the heat-insulating layer at multiple locations (for example, 10 locations) using a thickness measuring instrument (for example, a digital thickness gauge JAN-257 (probe Φ20) manufactured by Ozaki Seisakusho) can be cited.

[0097] The density of the heat insulating layer is not particularly limited, but is usually 0.2 to 0.5 g / cm 3 , preferably 0.3 g / cm 3 More preferably, 0.35 g / cm 3 More preferably, 0.37 g / cm 3 Above, preferably 0.45 g / cm 3 the following.

[0098] The thermal conductivity of the heat insulating layer at 80°C and 2MPa pressurized conditions is preferably 0.010W / K·m or more, preferably 0.3W / K·m or less, more preferably 0.1W / K·m or less, more preferably 0.08W / K·m or less, more preferably 0.06W / K·m or less, more preferably 0.055W / K·m or less, more preferably 0.045W / K·m or less, and further preferably 0.04W / K·m or less. The thermal conductivity of the heat insulating layer at 600°C and 2MPa pressurized conditions is preferably 0.010W / K·m or more, preferably 0.3W / K·m or less, more preferably 0.2W / K·m or less, more preferably 0.1W / K·m or less, more preferably 0.08W / K·m or less, and further preferably 0.075W / K·m or less.

[0099] When the heat insulating layer is prepared so that the thickness when not pressed is 2 mm, the thermal resistance under the conditions of 80°C and 2 MPa pressurization is preferably 0.020 (K·m 2 ) / W or more, more preferably 0.025(K·m 2 ) / W or more, more preferably 0.03(K·m 2 ) / W or more, more preferably 0.035(K·m2 ) / W or more, preferably 0.1(K·m 2 The thermal resistance of the initial 2 mm thick heat insulating layer under 600°C and 2 MPa pressure is preferably 0.010 (K·m 2 ) / W or more, more preferably 0.015(K·m 2 ) / W or more, more preferably 0.020(K·m 2 ) / W or more, preferably 0.1(K·m 2 ) / W or less.

[0100] The thermal conductivity of the heat insulating layer can be measured by the method described in Japanese Industrial Standard JIS A 1412-2:1999 “Methods for determination of thermal resistance and thermal conductivity of thermal insulating materials - Part 2: Heat flow meter method (HFM method)”.

[0101] It should be noted that the heat flow meter method (HFM method) is a secondary measurement method or comparative measurement method that compares a flat plate-shaped thermal insulation material (insulating layer) as a test body with a standard plate to measure heat transfer characteristics such as thermal conductivity and thermal resistance. The following describes the detailed measurement steps and measurement conditions.

[0102] The heat-insulating layer is cut into a specified size (e.g., 20 mm × 20 mm) to make a test body, and as a standard plate, an alumina composite material ("RS-100", manufactured by ZIRCAR Refractory Composites, Inc., thickness: 5 mm, thermal conductivity: 0.66 W / K·m) is prepared. Next, on the lower plate surface of the air pressure press, the first thermocouple, titanium plate, heat-insulating layer, titanium plate, second thermocouple, standard plate and third thermocouple are arranged in order from the top, and the upper plate and the lower plate are clamped to make the test body, standard plate, thermocouple, etc. close. Then, the upper plate and the lower plate are each heated to the specified measurement temperature, and then the test body is pressurized by applying a load to the test body through the air pressure press in such a way that the specified measurement pressure is reached.

[0103] It should be noted that, as the measurement temperature, the temperature of the upper plate on the first thermocouple side is set to 80° C., and the temperature of the lower plate on the third thermocouple side is set to 30° C. On the other hand, as the measurement temperature when set to high temperature conditions, the temperature of the upper plate on the first thermocouple side is set to 600° C., and the temperature of the lower plate on the third thermocouple side is set to 40° C.

[0104] In addition, as a measurement pressure, 2 MPa (load: 800 N) can be cited. The measurement can be continued in the state of heating and pressurization until the detection temperature of each thermocouple is stabilized, and the thermal conductivity k1 of the thermal insulation layer can be calculated by the following formula (I) based on the detection temperature of each thermocouple after the temperature is stabilized, the thickness of the thermal insulation layer during pressurization, the thermal conductivity of the standard plate, and the thickness of the standard plate during pressurization.

[0105] k1=k2×(L1×ΔT1) / (L2×ΔT2)……(I)

[0106] (Wherein, k1 is the thermal conductivity of the insulation layer [W / (m·K)], k2 is the thermal conductivity of the standard plate [W / (m·K)], L1 is the thickness of the insulation layer when pressurized, L2 is the thickness of the standard plate, ΔT1 is the temperature difference between the temperature of the second thermocouple and the temperature of the third thermocouple, and ΔT2 is the temperature difference between the temperature of the first thermocouple and the temperature of the second thermocouple.)

[0107] It should be noted that the term "the detected temperature is stable" means that the temperature change after 10 minutes is within a predetermined range (for example, within ±0.1° C.).

[0108] The thermal resistance of the heat insulating layer can be calculated by the following formula (II) based on the thermal conductivity k1 and the thickness L1 when pressed.

[0109] R1=L1 / k1……(II)

[0110] (Where R1 is the thermal resistance of the insulation layer [(m 2 ·K) / W], k1 is the thermal conductivity of the insulation layer [W / (m·K)], and L1 is the thickness of the insulation layer when pressurized.

[0111] There is no particular limitation on the compressive properties of the heat insulating layer, but it can be classified as a layer with a density of 300 kg / m 3 High-density insulation layer and density less than 300kg / m 3 Low density insulation layer.

[0112] The density of the insulation layer is 300kg / m 3 The compressive stress (compressive force [N] divided by the initial cross-sectional area of ​​the test body [MPa]) when the compressive strain is 25% in the case of the above high-density heat insulating layer is usually 1MPa to 5MPa, preferably 1.3MPa or more, more preferably 1.7MPa or more, further preferably 2.0MPa or more, preferably 4.5MPa or less, more preferably 4.0MPa or less, and further preferably 3.5MPa or less. It should be noted that the method for measuring the compressive stress can be listed as measuring by the same method as the buffer layer described later.

[0113] The density of the insulation layer is 300kg / m 3 In the case of the above high-density insulation layer, the compressive stress when the compressive strain is 50% is usually 4.0 MPa to 15 MPa, preferably 5.0 MPa or more, more preferably 6.0 MPa or more, further preferably 7.0 MPa or more, preferably 13 MPa or less, more preferably 11 MPa or less, further preferably 9.0 MPa or less.

[0114] The density of the insulation layer is 300kg / m 3 In the case of the above high-density insulation layer, the compressive stress when the compressive strain is 70% is usually 10 MPa to 25 MPa, preferably 11 MPa or more, more preferably 12 MPa or more, further preferably 13 MPa or more, preferably 23 MPa or less, more preferably 21 MPa or less, further preferably 19 MPa or less.

[0115] The density of the insulation layer is less than 300kg / m 3 In the case of a low-density insulation layer, the compressive stress when the compressive strain is 25% is usually 0.05 MPa to 1.0 MPa, preferably 0.1 MPa or more, more preferably 0.15 MPa or more, further preferably 0.20 MPa or more, preferably 0.7 MPa or less, more preferably 0.5 MPa or less, further preferably 0.3 MPa or less.

[0116] The density of the insulation layer is less than 300kg / m 3 In the case of a low-density insulation layer, the compressive stress when the compressive strain is 50% is generally 1.0 MPa to 4.0 MPa, preferably 1.3 MPa or more, more preferably 1.5 MPa or more, further preferably 1.7 MPa or more, preferably 3.5 MPa or less, more preferably 3.0 MPa or less, further preferably 2.5 MPa or less.

[0117] The density of the insulation layer is less than 300kg / m 3 In the case of a low-density insulation layer, the compressive stress when the compressive strain is 70% is generally 4.0 MPa to 10 MPa, preferably 4.5 MPa or more, more preferably 5.0 MPa or more, further preferably 5.5 MPa or more, preferably 9.0 MPa or less, more preferably 8.0 MPa or less, further preferably 7.0 MPa or less.

[0118] The number of the heat insulating layers is usually 1 or more, and usually 10 or less, preferably 7 or less, and more preferably 5 or less.

[0119] The heat insulating layer may be bonded to the adjacent layer by an adhesive or a binder, or may be bonded to the adjacent layer without an adhesive or a binder, preferably without an adhesive or a binder. Bonding without an adhesive or a binder, i.e., without using an adhesive or a binder, can reduce the thermal conductivity compared to the case of using an adhesive or a binder.

[0120] The shape of the heat insulating layer is not particularly limited, and the shape in plan view generally includes a rectangle (for example, a polygon such as a quadrilateral), a circle, an ellipse, and the like.

[0121] (Coating layer)

[0122] The covering layer is a layer composed of a resin film, and plays a role in suppressing the falling of silica particles and the like of the heat insulating layer and protecting the heat insulating layer.

[0123] The type of resin of the coating layer is not particularly limited. Specific examples include: polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyimide (PI), flame retardant polycarbonate (PC), breathable porous polyethylene (PE) with a molecular weight of 1 million to 7 million, flame retardant polyethylene (PE), biaxially stretched nylon film (Ny), etc.

[0124] The thickness of the coating layer is not particularly limited, and is usually 0.001 mm to 0.2 mm, preferably 0.005 mm or more, more preferably 0.007 mm or more, further preferably 0.010 mm or more, preferably 0.15 mm or less, more preferably 0.10 mm or less, and further preferably 0.050 mm or less. If the thickness of the coating layer is within the range, low thermal conductivity and mechanical strength can be taken into account. It should be noted that the thickness of the coating layer can be measured in the same manner as the thermal insulation layer.

[0125] The number of the coating layers is usually 1 or more, preferably 2 or more, usually 5 or less, preferably 4 or less, and more preferably 3 or less. It should be noted that the coating layer is formed by a sheet of resin film, and a sheet of resin film can be folded and inserted between the insulation layer and the buffer layer, respectively, to form two layers of coating layers. It is considered that the number of coating layers in the case of such folding is two layers.

[0126] In the case where the thermal insulation material is laminated with two or more coating layers, the two or more coating layers can clamp and enclose the thermal insulation layer from the thickness direction to seal the gap between the coating layers. It should be noted that the method of sealing the gap between the coating layers is not particularly limited, and generally, a sealing portion is provided at the outer edge of the coating layer so that the sealing portions between the coating layers are bonded to each other. The bonding method of the sealing portion is also not particularly limited, and welding using heat welding, ultrasonic welding, etc., and bonding using adhesives, bonding agents, etc. can be cited. In addition, the welding can be performed by directly welding the resin of the coating layer, or by separately providing a resin layer for welding.

[0127] The covering layer may be bonded to the adjacent heat insulating layer by means of an adhesive or a bonding agent, or may be bonded to the adjacent heat insulating layer without using an adhesive or a bonding agent. Preferably, the covering layer is bonded to the adjacent heat insulating layer without using an adhesive or a bonding agent.

[0128] When the insulating material is laminated with two or more coating layers and the two or more coating layers seal the gap between the coating layers, the coating layer preferably has a vent that connects the gap to the external space. By having the vent, shrink packaging or packaging using a deep-drawn film can be used as a packaging method.

[0129] The number of the vents in the covering layer is usually 1 or more, preferably 2 or more, and usually 50 or less, preferably 25 or less, and more preferably 10 or less.

[0130] The total opening area of ​​the vents in the coating layer is usually 0.000079 cm 2 ~10cm 2 , preferably 0.0001cm 2 More preferably 0.005 cm 2 More preferably, 0.01 cm 2 Above, preferably 5cm 2 Below, more preferably 4cm 2 Below, more preferably 3cm 2 If the total opening area of ​​the vents of the coating layer is within the above range, the coating layer can suppress the outflow of powder from the heat insulating layer.

[0131] The vents of the coating layer can also be covered with a breathable film. The air permeability of the breathable film is usually 4cm 3 / (cm 2 s)~500cm 3 / (cm 2 ·s), preferably 7cm 3 / (cm 2 ·s) or more, more preferably 10cm 3 / (cm 2 ·s) or more, more preferably 21cm3 / (cm 2 ·s) or more, preferably 250cm 3 / (cm 2 ·s) or less, more preferably 200cm 3 / (cm 2 ·s) or less, more preferably 100cm 3 / (cm 2 s) or below.

[0132] The heat insulating material may include layers other than the heat insulating layer and the coating layer, and may include a buffer layer that plays a role in compensating for the insufficient physical properties of the heat insulating layer alone. The buffer layer will be described in detail below.

[0133] The compressive elastic modulus (yield point stress / strain) of the buffer layer is usually 0.5 MPa to 20 MPa, preferably 0.7 MPa or more, more preferably 0.9 MPa or more, further preferably 1.1 MPa or more, preferably 18 MPa or less, more preferably 16 MPa or less, further preferably 14 MPa or less.

[0134] The compressive properties of the buffer layer are not particularly limited. The compressive stress of the buffer layer when the compressive strain is 25% is usually 0.1 MPa to 4 MPa, preferably 0.2 MPa or more, more preferably 0.3 MPa or more, further preferably 0.4 MPa or more, preferably 3.7 MPa or less, more preferably 3.5 MPa or less, further preferably 3.3 MPa or less.

[0135] The compressive stress of the buffer layer when the compressive strain is 50% is usually 0.3 MPa to 7 MPa, preferably 0.5 MPa or more, more preferably 0.6 MPa or more, further preferably 0.7 MPa or more, and preferably 6.5 MPa or less, more preferably 6.0 MPa or less, further preferably 5.5 MPa or less.

[0136] The compressive stress of the buffer layer when the compressive strain is 70% is usually 2 MPa to 15 MPa, preferably 2.3 MPa or more, more preferably 2.5 MPa or more, further preferably 2.7 MPa or more, preferably 14 MPa or less, more preferably 12 MPa or less, further preferably 10 MPa or less.

[0137] The compressive stress and compressive elastic modulus (yield point stress / strain) of the buffer layer can be measured using a precision universal testing machine such as Autograph. Specifically, the buffer layer can be cut into a predetermined size to form a test body (the cross-sectional area parallel to the surface perpendicular to the compression direction is used as the cross-sectional area used in the calculation of the compressive stress), and the compressive stress and displacement when the test body is compressed at a predetermined compression speed (e.g., 0.5 m / min) can be measured, and the calculation can be performed.

[0138] Examples of the cushion layer include a cushion layer composed of a fiber molded body containing fibers (hereinafter, sometimes simply referred to as a "fiber molded body") or a foamed molded body containing a foam (hereinafter, sometimes simply referred to as a "foamed molded body").

[0139] The fiber molded body is a molded body containing fibers, and the heat insulating layer is also preferably a molded body obtained by molding a mixture containing silica particles, inorganic fibers, and a non-polymeric dispersant. Therefore, when the heat insulating layer is a molded body, the difference between the molded body and the fiber molded body in the buffer layer can be judged by whether it contains silica particles. That is, the layer containing silica particles can be judged as the heat insulating layer, and the layer containing fibers without silica particles can be judged as the buffer layer. The fiber molded body in the buffer layer is preferably a molded body containing fibers but not containing silica particles.

[0140] The type of fiber contained in the fiber molding is not particularly limited, and can be classified into inorganic fibers and organic fibers in the same manner as the thermal insulation layer. As specific examples, inorganic fibers such as glass wool and rock wool, felt formed by cellulose fibers, polyester, polypropylene, etc., are listed, preferably inorganic fibers, and particularly preferably glass wool. Glass wool is a cured product comprising fibers and thermosetting resins, and the fibers are bonded to each other by thermosetting resins. In addition, it has the effect of increasing compressive stress and exerting a buffering function. It should be noted that the fiber molding may contain one type of fiber, or may contain two or more types of fibers. In addition, the aggregation form of the fibers may be any of non-woven fabrics, fabrics, woven fabrics, etc., usually in the state of non-woven fabrics.

[0141] The fiber content of the fiber molded body is not particularly limited, and is generally 50% to 99% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, preferably 97% by mass or less, more preferably 95% by mass or less, further preferably 93% by mass or less. If the fiber content is within the above range, the fiber molded body can easily exhibit cushioning properties.

[0142] The average fiber length of the fibers contained in the fiber molding is not particularly limited, and is usually 1 mm to 200 mm, preferably 5 mm or more, more preferably 10 mm or more, and further preferably 20 mm or more, and preferably 175 mm or less, more preferably 150 mm or less, and further preferably 125 mm or less. If the average fiber length of the fibers is within the above range, the cushioning properties are easily exerted.

[0143] The average fiber diameter of the fibers contained in the fiber molded body is not particularly limited, and is generally 3 μm to 13 μm, preferably 4 μm or more, more preferably 4.5 μm or more, further preferably 5 μm or more, preferably 10 μm or less, more preferably 9 μm or less, further preferably 8 μm or less. If the average fiber diameter of the fibers is within the above range, the fiber molded body can easily achieve both cushioning properties and low thermal conductivity.

[0144] The fiber molded product is a molded product containing fibers, and preferably contains a binder (adhesive) in addition to the fibers. The type of the binder contained in the fiber molded product is not particularly limited, and can be classified into organic binders and inorganic binders.

[0145] Specific examples of organic binders include thermoplastic resins, thermoplastic elastomers, thermosetting resins, thermosetting elastomers, sugars, water-soluble polymers, etc. Specific examples of inorganic binders include aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide, calcium oxide, etc. If the binder is the above-mentioned binder, the shape stability is improved. It should be noted that the fiber molding may contain one binder or two or more binders.

[0146] The content of the binder in the fiber molding is not particularly limited, and is generally 1% to 50% by mass, preferably 2% by mass or more, more preferably 5% by mass or more, and further preferably 7% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, and further preferably 20% by mass or less. When the content of the binder is within the above range, the thermal conductivity is low and the cushioning property is good.

[0147] The fiber molded body is a molded body containing fibers, preferably a molded body obtained by molding a mixture containing fibers and a binder but not containing hydrophilic fumed silica. It should be noted that among the fibers used for the fiber molded body, there are fibers sold in a state where a thermosetting resin as a binder is dispersed, and such fibers can be made into a fiber molded body by heating and compressing after being cut into a target shape.

[0148] The foamed molded body is a molded body containing a foamed body. The material of the foamed body is usually a resin such as a thermoplastic resin or a thermosetting resin. The foamed body can be molded by appropriately using a known molding method and conditions.

[0149] The type of resin of the foam contained in the foam molded body is not particularly limited. Specific examples include: polyolefin resins such as polyethylene and polypropylene, styrene resins such as polyethylene terephthalate resin, vinyl chloride resin (PVC), and polystyrene, polyurethane resins such as polyurethane resin, resol type phenolic resins such as phenolic resin (PF), melamine resins such as melamine resin (MF), epoxy resins such as epoxy resin (EP), and other foaming foams.

[0150] The cell structure of the foamed molded article may be closed cells or open cells, and can be appropriately selected depending on the target physical properties and the like.

[0151] When the thermal insulation material includes a buffer layer, the thickness of the buffer layer is generally 0.5 to 10 mm, preferably 1 mm or more, more preferably 1.5 mm or more, further preferably 2 mm or more, preferably 7 mm or less, more preferably 6 mm or less, further preferably 5 mm or less. If the thickness of the buffer layer is within the range, the stress caused by battery expansion can be appropriately buffered. It should be noted that the thickness of the buffer layer can be measured in the same way as the thermal insulation layer, and can be measured by using a thickness gauge (digital thickness gauge JAN-257, probe Φ20, manufactured by Ozaki Manufacturing Co., Ltd.) to measure the thickness of the cross section of the buffer layer, and then the average value of the numerical group obtained by performing the measurement at any 10 locations is adopted.

[0152] The thermal conductivity of the buffer layer is not particularly limited. Under the conditions of 80°C and 2MPa, it is preferably 0.030W / K·m or more, more preferably 0.040W / K·m or more, and further preferably 0.050W / K·m or more, and preferably 0.2W / K·m or less, more preferably 0.15W / K·m or less, and further preferably 0.1W / K·m or less. The thermal conductivity of the buffer layer under the conditions of 600°C and 2MPa is preferably 0.04W / K·m or more, more preferably 0.05W / K·m or more, further preferably 0.06W / K·m or more, preferably 0.30W / K·m or less, more preferably 0.25W / K·m or less, and further preferably 0.20W / K·m or less. It should be noted that the thermal conductivity can be measured by the same method as the method for measuring the thermal conductivity of the thermal insulation material described later.

[0153] The thermal resistance of the buffer layer is not particularly limited, but is preferably 0.020 (K·m 2 ) / W or more, more preferably 0.025(K·m 2 ) / W or more, more preferably 0.03(K·m 2 ) / W or more, preferably 0.07(K·m 2) / W or less, more preferably 0.06(K·m 2 ) / W or less, more preferably 0.05(K·m 2 The thermal resistance of the heat insulating layer at 600°C and 2 MPa is preferably 0.001 (K·m 2 ) / W or more, more preferably 0.003(K·m 2 ) / W or more, more preferably 0.005(K·m 2 ) / W or more, preferably 0.1(K·m 2 ) / W or less, more preferably 0.05(K·m 2 ) / W or less, more preferably 0.01(K·m 2 ) / W or less. It should be noted that the thermal resistance can be measured by the same method as the method for measuring the thermal resistance of the thermal insulation material described later.

[0154] The number of buffer layers is usually 10 or less, preferably 5 or less, more preferably 3 or less, and may be 2 or 1.

[0155] The buffer layer may be bonded to the adjacent layer by an adhesive or a binder, or may be bonded to the adjacent layer without an adhesive or a binder, preferably without an adhesive or a binder. Bonding without an adhesive or a binder, i.e., without using an adhesive or a binder, can suppress an increase in thermal conductivity compared to a case where an adhesive or a binder is used.

[0156] The shape of the buffer layer is not particularly limited, and the shape in plan view generally includes a rectangle (for example, a polygon such as a quadrilateral), a circle, an ellipse, and the like.

[0157] The thermal insulation material of the embodiment of the present invention is not particularly limited as long as it satisfies the above conditions. The thermal conductivity of the thermal insulation material at 80°C and 2MPa is preferably 0.02W / K·m or more, more preferably 0.03W / K·m or more, and further preferably 0.04W / K·m or more, preferably 0.2W / K·m or less, more preferably 0.15W / K·m or less, and further preferably 0.10W / K·m or less. It should be noted that the thermal conductivity can be measured by the same method as the thermal insulation layer.

[0158] The thermal resistance of the thermal insulation material under the conditions of 80°C and 2 MPa when prepared so that the thickness when not pressed is 2 mm is not particularly limited, but is preferably 0.01 (K·m 2 ) / W or more, more preferably 0.02(K·m 2 ) / W or more, more preferably 0.03(K·m 2 ) / W or more, preferably 0.10(K·m2 ) / W or less, more preferably 0.09(K·m 2 ) / W or less, more preferably 0.08(K·m 2 ) / W or less. The thermal resistance can be measured by the same method as that of the heat insulating layer.

[0159] The use of the insulating material of the embodiment of the present invention is not particularly limited, and can be appropriately used for known uses of insulating materials. It is particularly preferably used as an insulating material between single cells arranged in a battery module, and more specifically, it is particularly preferably used as an insulating material between single cells arranged in a lithium-ion battery module.

[0160] Figure 1 is a perspective view schematically showing an example of a battery module in which a heat insulating material according to an embodiment is arranged between single cells. Figure 2 yes Figure 1 The II-II line cross-sectional view. Figure 1 As shown, the battery module 50 includes a plurality of cells (here, square cells) 51 arranged in the thickness direction, and a heat insulating material 52 is arranged between each cell 51. The plurality of cells 51 arranged with the heat insulating material 52 sandwiched between them are usually restrained in a state where a pressing force (compression force) is applied in the thickness direction via restraining plates 52a, 52a arranged at both ends, and are stored in a battery box 53 for use.

[0161] like Figure 2 As shown, the insulating material 52 has the following structure: a stacked insulating layer 521 and a buffer layer 522, which are sandwiched and wrapped by two resin films (two coating layers) 523A and 523B from the thickness direction. The resin films 523A and 523B are sealed by bonding (for example, heat welding) at the sealing parts set along their outer edges to form a coating material 523 as a whole. By sandwiching the insulating material 52 of the above structure between two adjacent single cells 51 and 51, the effect of insulating the opposing surfaces 51a and 51a of the two single cells 51 and 51 is achieved. It should be noted that in Figure 2 FIG. 5 shows a structure in which two buffer layers 522A and 522B are stacked and arranged in a coating material 523. The number of buffer layers can be one or more than two. The two or more buffer layers can also be separately arranged on both sides of the insulation layer. Figure 2 The structure with only one insulating layer 521 is shown in FIG. 5 , and the number of insulating layers may be more than two. In addition, the buffer layer may be arranged on the outside of the covering material, and the plurality of buffer layers may be separately arranged on the outside and inside of the covering material. A vent may also be provided in the covering material 523.

[0162] Several possible solutions for thermal insulation materials are illustrated below in more detail.

[0163] Figure 3 is a perspective view schematically showing a heat insulating material according to one embodiment, Figure 4 yes Figure 3 IV-IV line cross-sectional view. Figure 4 As shown, the insulating material 1 has the following structure: an insulating layer 10 composed of two insulating layers 10A and 10B is stacked on one surface 20a of the buffer layer 20, and they are sandwiched and wrapped by two resin films (two coating layers) 31A and 31B from the thickness direction. The resin films 31A and 31B are sealed by bonding (for example, heat welding) at the sealing part 32 set along their outer edges to form a coating material 30 as a whole. The resin film 31A is formed into a convex shape that roughly covers the end surface of the stack of the insulating layer 10 and the buffer layer 20, and a vent (through hole) 33 is formed in the part covering the end surface. A vent film 34 for preventing powder from flowing out of the insulating layer is arranged at the opening of the vent 33 facing the outside. When the insulating material 1 is arranged between the above-mentioned single cells in a battery module having a plurality of single cells arranged in the thickness direction, for example, Figure 4 The Z direction (thickness direction of the insulating material 1) shown becomes the arrangement direction of the above-mentioned single cells, and the Y direction becomes the electrode extraction direction of the above-mentioned single cells, that is, the insulating material 1 is configured and used in a manner in which the opening direction (X direction) of the vent hole is inconsistent with the electrode extraction direction of the single cell.

[0164] Figure 5 2 is a cross-sectional view schematically showing another embodiment of the heat insulating material. In this embodiment, two heat insulating layers 10A and 10B constituting the heat insulating layer 10 are separately stacked on one surface 20a and the other surface 20b of the buffer layer 20. The heat insulating material 1 of this configuration has high structural symmetry with respect to the thickness direction, and it is also easy to suppress the temperature difference between the two surfaces, so it may be advantageous from the perspective of preventing deformation (such as warping deformation) of the heat insulating material. It should be noted that, as Figure 6 As shown in the embodiment example, the buffer layer 20 may be a laminated structure consisting of two layers of buffer layers 20A and 20B, or a laminated structure of three or more layers. In addition, the inner surface 10a of the heat insulating layer 10A may be bonded to the buffer material 20 or not. The bonding of the inner surface of the heat insulating layer 10B to the buffer material 20 is also the same.

[0165] Figure 72 is a cross-sectional view schematically showing another embodiment of a heat insulating material. In this embodiment, the heat insulating layer 10 is wrapped in the covering material 30, and the buffer material 20 is arranged outside the covering material 30. More specifically, one surface 20a of the buffer material 20 is fixed to one surface of the covering material 30 by means of an adhesive layer 40 formed of an adhesive or a bonding agent. The heat insulating material disclosed herein can also be implemented in this manner.

[0166] It should be noted that the target cell is not limited to a square cell, and may be, for example, a laminated cell or a cylindrical cell. The shape of the heat insulating material may be appropriately adopted depending on the type of cell.

[0167] In addition, the battery target devices include electric vehicles such as electric vehicles (EV), hybrid vehicles (HV), and plug-in hybrid vehicles (PHV), portable electronic devices such as portable terminals, mobile phones, and notebook personal computers, and wearable devices.

[0168] (Method for producing thermal insulation material)

[0169] The method for producing the thermal insulating material is not particularly limited, and the thermal insulating material can be produced by appropriately adopting a known process. Examples of the production method generally include the following steps.

[0170] Mixing step: A step of mixing silica particles, inorganic fibers, and at least one of the non-polymeric dispersants represented by the following formula (A1), (A2), (A3), or (A4) in a solvent to obtain a mixed solution.

[0171] ·Coating step: A step of applying the mixed solution obtained in the mixing step to obtain a coating film.

[0172] A step of forming the coating film obtained in the coating step to obtain a heat insulating layer.

[0173]

[0174] (In formulas (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a heteroatom. 1 , R 2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 1 , R 2 , R 3 and R 4The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 5 represents a hydrocarbon group optionally containing a heteroatom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a heteroatom or a hydrogen atom. 5 , R 6 and R 7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 5 , R 6 and R 7 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 8 and R 9 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

[0175] Hereinafter, the mixing step, the coating step, the molding step, etc. will be described in detail.

[0176] The mixing step is a step of mixing silica particles, inorganic fibers, and at least one of the non-polymeric dispersants shown in formula (A1), (A2), (A3) or (A4) in a solvent to obtain a mixed solution. This is a so-called wet method. Specifically, it is a step of mixing silica particles, inorganic fibers, and non-polymeric dispersants in a solvent to prepare a mixed solution (slurry state). The mixing in the mixing step can be, for example, using a disperser, Labo Plastomill, tri mix, planetary mixer, kneader, etc.

[0177] The type of solvent is not particularly limited, and examples thereof include protic solvents such as alcohols, amides, and water; and aprotic solvents such as esters, ketones, nitriles, and ethers.

[0178] The surface tension of the solvent is not particularly limited, and is generally 20 mN / m to 73 mN / m, preferably 21 mN / m or more, preferably 50 mN / m or less, more preferably 40 mN / m or less, and further preferably 30 mN / m or less. If the surface tension of the solvent is within the range, thermal insulation and mechanical strength are good. It should be noted that the method for measuring the surface tension of the solvent can be listed as measuring by the ring method.

[0179] In the mixing process, the amount of the non-polymeric dispersant coordinated in the mixed solution is not particularly limited, and it can be considered that the effect of use and the influence on other characteristics are appropriately set. The amount of the dispersant in the mixed solution can be, for example, more than 0.0001 mass parts relative to the amount of 100 mass parts of silicon dioxide particles contained in the mixed solution, from the viewpoint of easily obtaining a higher effect of use, it can be more than 0.0005 mass parts, can be more than 0.001 mass parts, or can be more than 0.05 mass parts. In addition, the amount of the dispersant in the mixed solution can be, for example, less than 10 mass parts relative to the amount of 100 mass parts of silicon dioxide particles contained in the mixed solution, from the viewpoint of easily avoiding the influence on other characteristics, it is usually suitable for less than 5 mass parts (for example, more than 0.0001 mass parts and less than 5 mass parts), it is advantageous for less than 3 mass parts, it can be less than 2 mass parts, it can be less than 1 mass part, it can be less than 1 mass part (for example, less than 0.8 mass parts). In some embodiments, the amount of the dispersant in the mixed solution is generally 0.05 to 5 parts by mass relative to 100 parts by mass of the silica particles contained in the mixed solution, preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, further preferably 0.5 parts by mass or more, and preferably 2 parts by mass or less. If the amount of the non-polymeric dispersant is within the above range, the mixed solution is dispersed stably and the thermal insulation of the thermal insulation material is good.

[0180] The mixing temperature is not particularly limited, but is usually 20° C. or higher and below the boiling point of the solvent, preferably 22° C. or higher, preferably 50° C. or lower, more preferably 40° C. or lower, and further preferably 30° C. or lower. When the mixing temperature is within the above range, the solvent (e.g., organic solvent) is less likely to volatilize and the blending ratio is less likely to change.

[0181] The mixing time is not particularly limited, but is usually 1 minute to 5 hours, preferably 5 minutes or more, preferably 4 hours or less, more preferably 2 hours or less, and further preferably 1 hour or less. If the mixing time is within the above range, the thermal insulation material can be efficiently produced.

[0182] The cone penetration of the mixed solution is not particularly limited, and is usually 50 to 200, preferably 55 or more, more preferably 60 or more, and further preferably 65 or more, and preferably 180 or less, more preferably 160 or less, and further preferably 140 or less. If the cone penetration of the mixed solution is within the above range, fiber breakage can be reduced when the fibers are uniformly dispersed.

[0183] It should be noted that the method for measuring the cone penetration of the mixed liquid can be listed as the method described in Japanese Industrial Standard JIS K 2220:2013 "Grease-Part VII: Cone Penetration Test Method", and in particular, the method of measuring by "unworked penetration" can be listed. Measuring equipment that can measure cone penetration is commercially available, and specifically, PENETRO METER manufactured by Nikka-engineering can be listed. As a measuring step, a crucible of a size that does not contact the weight when the cone weight is lowered is prepared, and the mixed liquid is filled therein, and is arranged in a measuring equipment equipped with a weight. Next, the position of the weight is adjusted to the position where the weight contacts the mixed liquid, and the position is set to 0 point. Then, at room temperature (25°C), the weight is lowered for 5 seconds (±0.1 seconds), and the depth (mm) × 10 of the weight that falls into the mixed liquid is calculated as the cone penetration. The cone weight may be a standard cone defined in Japanese Industrial Standards, and may have a total weight of 102.5 g ± 0.05 g and a weight holder of 47.5 ± 0.05 g.

[0184] The coating method and coating conditions in the coating step are not particularly limited, and a known method may be appropriately adopted, and examples thereof include coating using a notch wheel coater, spin coater, die coater, roll coater, calendar roll, dispenser, and the like.

[0185] The molding method and molding conditions in the molding step are not particularly limited, and a known method can be appropriately adopted. For example, a method of molding a film having a density of 0.3 to 0.5 g / cm 3 The drying conditions are preferably 60° C. to 150° C. The drying time is preferably 4 minutes to 20 minutes.

[0186] As can be seen from the above description and the following embodiments, the matters disclosed in this specification include the following matters.

[0187] [1] A thermal insulation material comprising a thermal insulation layer, wherein the thermal insulation layer contains silica particles, inorganic fibers, and at least one of the non-polymeric dispersants represented by the following formula (A1), (A2), (A3) or (A4), wherein the silica particles have a BET specific surface area of ​​90 m 2 / g or more and less than 380m 2 / g.

[0188]

[0189] (In formulas (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 1 , R 2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 1 , R 2 , R 3 and R 4 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 5 represents a hydrocarbon group optionally containing a heteroatom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a heteroatom or a hydrogen atom. 5 , R 6 and R 7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 5 , R 6 and R 7 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 8 and R 9 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

[0190] [2] A thermal insulation material comprising a thermal insulation layer, wherein the thermal insulation layer contains silica particles, inorganic fibers, and at least one of the non-polymeric dispersants represented by the following formula (A1), (A2), (A3) or (A4), wherein the silica particles have a BET specific surface area of ​​90 m 2 / g or more and less than 380m 2 / g.

[0191]

[0192] (In formulas (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a nitrogen atom, and R 1 , R 2 , R 3 and R4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 12 to 40. 1 , R 2 , R 3 and R 4 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 5 represents a hydrocarbon group optionally containing a nitrogen atom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a nitrogen atom or a hydrogen atom, and R 5 , R 6 and R 7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 12 to 40. 5 , R 6 and R 7 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 8 and R 9 Each independently represents a hydrocarbon group optionally containing a nitrogen atom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 12 to 40. 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

[0193] [3] The thermal insulation material according to [1] or [2] above, wherein the content of the non-polymeric dispersant in the thermal insulation layer is 0.01% by mass to 5% by mass.

[0194] [4] The thermal insulation material according to any one of [1] to [3] above, wherein the silica particles are at least one selected from the group consisting of dry silica, wet silica, and silica aerogel.

[0195] [5] The thermal insulation material according to any one of [1] to [3] above, wherein the silica particles are at least one selected from the group consisting of hydrophilic fumed silica and hydrophobic fumed silica.

[0196] [6] The thermal insulation material according to any one of [1] to [5] above, wherein the average primary particle size of the silica particles is 100 nm or less.

[0197] [7] The thermal insulation material according to any one of [1] to [6] above, wherein the inorganic fiber is at least one selected from the group consisting of glass fibers and biosoluble inorganic fibers.

[0198] [8] The thermal insulation material according to any one of [1] to [7] above, wherein the density of the thermal insulation layer is 0.2 g / cm 3 ~0.5g / cm 3 .

[0199] [9] The thermal insulation material according to any one of [1] to [8] above, wherein the thermal conductivity of the thermal insulation layer under pressure conditions of 80° C. and 2 MPa is 0.045 W / (m·K) or less.

[0200]

[10] The thermal insulation material according to any one of [1] to [9] above, wherein the thermal conductivity of the thermal insulation layer under 600° C. and 2 MPa pressure conditions is 0.08 W / (m·K) or less.

[0201]

[11] The thermal insulation material according to any one of [1] to

[10] above, further comprising a covering layer formed of a resin film, wherein the thermal insulation material is a laminate of the thermal insulation layer and the covering layer.

[0202]

[12] The thermal insulation material according to

[11] above, wherein the thermal insulation material is stacked with two or more of the coating layers, and the two or more coating layers sandwich and enclose the thermal insulation layer from a thickness direction to seal the gaps between the coating layers.

[0203]

[13] The thermal insulation material according to

[12] above, wherein the coating layer has a vent that connects the gap to an external space.

[0204]

[14] The thermal insulation material according to any one of [1] to

[13] , which is arranged between single cells in a battery module.

[0205]

[15] A method for manufacturing an insulating material, comprising: a mixing step of mixing silica particles, inorganic fibers and a non-polymer dispersant represented by the following formula (A1), (A2), (A3) or (A4) in a solvent to obtain a mixed liquid; a coating step of coating the mixed liquid obtained in the mixing step to obtain a coating film; and a molding step of molding the coating film obtained in the coating step to obtain a thermal insulating layer.

[0206]

[0207] (In formulas (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 1 , R 2 , R 3 and R4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 1 , R 2 , R 3 and R 4 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 5 represents a hydrocarbon group optionally containing a heteroatom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a heteroatom or a hydrogen atom. 5 , R 6 and R 7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 5 , R 6 and R 7 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 8 and R 9 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40. 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

[0208]

[16] A method for manufacturing an insulating material, comprising: a mixing step of mixing silica particles, inorganic fibers and a non-polymer dispersant represented by the following formula (A1), (A2), (A3) or (A4) in a solvent to obtain a mixed liquid; a coating step of coating the mixed liquid obtained in the mixing step to obtain a coating film; and a molding step of molding the coating film obtained in the coating step to obtain a thermal insulating layer.

[0209]

[0210] (In formulas (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a nitrogen atom, and R 1 , R 2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 12 to 40. 1 , R 2 , R 3 and R 4 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 5represents a hydrocarbon group optionally containing a nitrogen atom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a nitrogen atom or a hydrogen atom, and R 5 , R 6 and R 7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 12 to 40. 5 , R 6 and R 7 The hydrocarbon groups of are optionally bonded to each other to form a ring structure. 8 and R 9 Each independently represents a hydrocarbon group optionally containing a nitrogen atom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 12 to 40. 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

[0211]

[17] The method for producing a thermal insulation material according to

[15] or

[16] above, wherein the amount of the non-polymer dispersant added to the mixed liquid is 0.05 to 5 parts by mass relative to 100 parts by mass of the silica particles.

[0212]

[18] The method for producing a thermal insulation material according to any one of

[15] to

[17] above, wherein the solvent is a protic solvent.

[0213]

[19] The method for producing a thermal insulation material according to any one of

[15] to

[18] above, wherein the surface tension of the solvent is less than 73 mN / m.

[0214] [Example]

[0215] <<Experimental Example 1>>

[0216] <Manufacturing of thermal insulation materials (insulation layers)>

[0217] (Example 1)

[0218] Hydrophilic fumed silica ("AEROSIL (registered trademark) 200", manufactured by AEROSIL Japan, average primary particle size: about 12 nm, BET specific surface area: 200 m) was added to a mixed solvent (surface tension: 23 mN / m) of 300 parts by mass of isopropyl alcohol (IPA, surface tension: 21 mN / m) as a protic solvent and 60 parts by mass of water (surface tension: 73 mN / m). 2 / g) 100 parts by mass, glass fiber ("CS 6J-888", manufactured by Nitto Bosho Co., Ltd., average fiber length: 6 mm, average fiber diameter: 11 μm) as an inorganic fiber 20 parts by mass, "QUARTAMIN 24P" manufactured by Kao Corporation as a dispersant containing a non-polymer type dispersant (active ingredient: dodecyltrimethylammonium chloride (C 12 H 25 N + (CH3)3Cl)), active ingredient content: 27% by mass), 1.9 parts by mass (0.5 parts by mass as active ingredient (ammonium salt)), are mixed in such a way that the cone penetration becomes 70-140. It should be noted that the above-mentioned dispersant, in addition to the non-polymer dispersant as the active ingredient, also contains a solvent such as water (dispersion medium) as the remainder. In this example and the following examples, "active ingredient" refers to the non-polymer or polymer dispersant components, surfactant components, etc. in the dispersant products used in each example. In addition, for the obtained mixed solution, the cone penetration measurement and dispersion stability described later are evaluated. Next, the obtained mixed solution is applied to a substrate in such a way that the thickness becomes 2 mm to form a coating film. Furthermore, the coating film is made to have a thickness of 1 mm and a density of 0.3-0.5 g / cm 3 The mixture containing hydrophilic fumed silica, glass fiber and non-polymeric dispersant was compressed and molded by a hot press, and then dried at 100°C for 10 minutes to produce a molded product, namely a thermal insulation material (thermal insulation layer). It should be noted that the thickness of the obtained thermal insulation material (thermal insulation layer) is 1 mm and the density is 0.37 g / cm 3 .

[0219] Next, the content of dodecyltrimethylammonium chloride contained in the obtained insulating material (insulating layer) is determined by liquid chromatography-mass spectrometry (LC / MS). First, standard solutions of various concentrations in which QUARTAMIN24P is dissolved are prepared to make a standard curve of the concentration of dodecyltrimethylammonium chloride and the area value of LC / MS. Next, 0.05g of insulating material is collected, added to 25mL of a 1:1 (volume ratio) mixed solution of ultrapure water / ethanol, and shaken for more than 1 hour to extract the dodecyltrimethylammonium chloride contained in the insulating material. The obtained solution is passed through a membrane filter (0.20μm) and put into LC / MS, and the content of dodecyltrimethylammonium chloride in the solution is determined according to the previous standard curve. The content of dodecyltrimethylammonium chloride contained in the insulating material is calculated based on the content of dodecyltrimethylammonium chloride contained in 0.05g of the insulating material, and the result is 0.31% by mass.

[0220] In addition, the conditions of LC / MS measurement are as follows.

[0221] Measuring apparatus: High performance liquid chromatography-mass spectrometer (manufactured by Thermo Fisher Scientific, UltiMate 3000 / TSQ QUANTUMACCESS MAX).

[0222] Chromatographic column: "L-column3 C18" manufactured by the Institute for Evaluation of Chemical Substances.

[0223] The eluent composition was pure water (with ammonium acetate added) / acetonitrile gradient conditions.

[0224] Flow rate: 0.6mL / min.

[0225] Detector: MS (full scan: 100-500, m / z=228).

[0226] Column temperature: 40℃.

[0227] Injection volume: 5 μL.

[0228] Ionization method: ESI (POS.).

[0229] Ion spray voltage: 3.0 kV.

[0230] Evaporation temperature: 350℃.

[0231] Capillary temperature: 270°C.

[0232] (Example 2)

[0233] A thermal insulation material having a thickness of 1 mm was produced in the same manner as in Example 1 except that the amount of QUARTAMIN 24P was changed to 0.05 parts by mass based on 100 parts by mass of the hydrophilic fumed silica.

[0234] (Example 3)

[0235] A thermal insulation material having a thickness of 1 mm was produced in the same manner as in Example 1 except that the amount of QUARTAMIN 24P was changed to 1 part by mass based on 100 parts by mass of the hydrophilic fumed silica, using dodecyltrimethylammonium chloride as the non-polymeric dispersant.

[0236] (Example 4)

[0237] A thermal insulation material having a thickness of 1 mm was prepared in the same manner as in Example 1 except that the amount of QUARTAMIN 24P was changed to 2 parts by mass based on 100 parts by mass of the hydrophilic fumed silica, using dodecyltrimethylammonium chloride as the non-polymeric dispersant.

[0238] (Example 5)

[0239] A thermal insulation material having a thickness of 1 mm was produced in the same manner as in Example 1 except that the amount of QUARTAMIN 24P was changed to 3 parts by mass based on 100 parts by mass of the hydrophilic fumed silica, using dodecyltrimethylammonium chloride as the non-polymeric dispersant.

[0240] (Example 6)

[0241] A thermal insulation material having a thickness of 1 mm was produced in the same manner as in Example 1 except that the amount of QUARTAMIN 24P was changed to 5 parts by mass based on 100 parts by mass of the hydrophilic fumed silica, using dodecyltrimethylammonium chloride as the non-polymeric dispersant.

[0242] (Example 7)

[0243] A thermal insulation material having a thickness of 1 mm was produced by the same method as in Example 1, except that the dodecyltrimethylammonium chloride as the non-polymer dispersant in Example 1 was changed to hexadecyl(C16)trimethylammonium chloride ("QUARTAMIN 60W" manufactured by Kao Corporation, 0.5 parts by mass as the active ingredient (ammonium salt)).

[0244] (Example 8)

[0245] A thermal insulation material having a thickness of 1 mm was produced by the same method as in Example 1, except that the dodecyltrimethylammonium chloride as the non-polymer dispersant in Example 1 was changed to octadecyl(C18)trimethylammonium chloride ("QUARTAMIN 86W" manufactured by Kao Corporation, 0.5 parts by mass as the active ingredient (ammonium salt)).

[0246] (Example 9)

[0247] A thermal insulation material having a thickness of 1 mm was produced by the same method as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymer dispersant in Example 1 was replaced with behenyl (C22)trimethylammonium chloride (“LIPOQUAD22-80” manufactured by Lion Specialty Chemicals, 0.5 parts by mass as the active ingredient (ammonium salt)).

[0248] (Example 10)

[0249] A thermal insulation material having a thickness of 1 mm was produced by the same method as in Example 1, except that the dodecyltrimethylammonium chloride as the non-polymer dispersant in Example 1 was replaced with dodecyl(C12)ethyldimethylammoniumethylsulfate (“CATIOGEN ES-L” manufactured by Daiichi Kogyo Seiyaku Co., Ltd., 0.5 parts by mass as the active ingredient (ammoniumethylsulfate)).

[0250] (Example 11)

[0251] A thermal insulation material having a thickness of 1 mm was produced by the same method as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymer dispersant in Example 1 was replaced with dodecyl(C12)benzyldimethylammonium chloride ("CATIOGEN BC-50" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., 0.5 parts by mass as the active ingredient (ammonium salt)).

[0252] (Example 12)

[0253] A thermal insulation material having a thickness of 1 mm was prepared by the same method as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with dodecyl(C12)amine ("LipoMin12D" manufactured by Lion Specialty Chemicals, 0.5 parts by mass as the active ingredient (amine)).

[0254] (Example 13)

[0255] A thermal insulation material having a thickness of 1 mm was prepared by the same method as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymer dispersant in Example 1 was replaced with dodecyl(C12)dimethylamine ("LipoMin DM12D" manufactured by Lion Specialty Chemicals, 0.5 parts by mass as the active ingredient (amine)).

[0256] (Example 14)

[0257] A thermal insulation material having a thickness of 1 mm was prepared by the same method as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymer dispersant in Example 1 was replaced with octadecyl (C18) amine ("LipoMin18D" manufactured by Lion Specialty Chemicals, 0.5 parts by mass as the active ingredient (amine)).

[0258] (Example 15)

[0259] A thermal insulation material having a thickness of 1 mm was prepared by the same method as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with hexadecyl (C16) dimethylamine ("LipoMin DM16D" manufactured by Lion Specialty Chemicals, 0.5 parts by mass as the active ingredient (amine)).

[0260] (Example 16)

[0261] The hydrophilic fumed silica AEROSIL (registered trademark) 200 in Example 1 was replaced with AEROSIL (registered trademark) 90G (manufactured by AEROSIL Japan, average primary particle size: about 20 nm, BET specific surface area: 90 m 2 / g), except for this, a thermal insulation material with a thickness of 1 mm was produced by the same method as in Example 1.

[0262] (Example 17)

[0263] The hydrophilic fumed silica AEROSIL (registered trademark) 200 in Example 1 was replaced with AEROSIL (registered trademark) 130 (manufactured by AEROSIL Japan, average primary particle size: about 16 nm, BET specific surface area: 130 m 2 / g), except for this, a thermal insulation material with a thickness of 1 mm was produced by the same method as in Example 1.

[0264] (Comparative Example 1)

[0265] The hydrophilic fumed silica AEROSIL (registered trademark) 200 in Example 1 was replaced with AEROSIL (registered trademark) 50 (manufactured by AEROSIL Japan, average primary particle size: 30 nm, BET specific surface area: 50 m 2 / g), except for this, a thermal insulation material with a thickness of 1 mm was produced by the same method as in Example 1.

[0266] (Comparative Example 2)

[0267] The hydrophilic fumed silica AEROSIL (registered trademark) 200 in Example 1 was replaced with AEROSIL (registered trademark) 380 (manufactured by AEROSIL Japan, average primary particle size: about 7 nm, BET specific surface area: 380 m 2 / g), except for this, a thermal insulation material with a thickness of 1 mm was produced by the same method as in Example 1.

[0268] (Comparative Example 3)

[0269] A thermal insulation material having a thickness of 1 mm was prepared in the same manner as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymer dispersant in Example 1 was replaced with a special polycarboxylic acid polymer surfactant ("DEMOL P" manufactured by Kao Corporation, 0.5 parts by mass as the active ingredient).

[0270] (Comparative Example 4)

[0271] A thermal insulation material having a thickness of 1 mm was produced in the same manner as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with a nonionic surfactant ("SN WET S" manufactured by Sannopco, 0.5 parts by mass as the active ingredient).

[0272] (Comparative Example 5)

[0273] A thermal insulation material having a thickness of 1 mm was produced in the same manner as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with an amphoteric dispersant ("BYK-191" manufactured by BYK-Chemie Japan, 0.5 parts by mass as the active ingredient).

[0274] (Example 18)

[0275] A heat insulating material having a thickness of 1 mm was produced in the same manner as in Example 1 except that 1.5 parts by mass of graphite "BF-3AK" (manufactured by Chuetsu Graphite Industry Co., Ltd., average particle size: 3 μm) was added to the formulation of Example 12.

[0276] (Example 19)

[0277] A heat insulating material having a thickness of 1 mm was produced in the same manner as in Example 1 except that 1.5 parts by mass of carbon powder "SLC-1" (manufactured by SEC Carbon, average particle size: 1 μm) was added to the formulation of Example 12.

[0278] (Example 20)

[0279] A thermal insulation material having a thickness of 1 mm was produced in the same manner as in Example 1, except that 1.5 parts by mass of carbon black "MA100" (manufactured by Mitsubishi Chemical Co., Ltd., average particle size: 24 nm, DBP oil absorption: 100 mL / 100 g) was added to the formulation of Example 15.

[0280] (Example 21)

[0281] A thermal insulation material having a thickness of 1 mm was produced in the same manner as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with octyl (C8) amine ("Lipomin 8D" manufactured by Lion Specialty Chemicals, 0.5 parts by mass as an active ingredient).

[0282] (Example 22)

[0283] A thermal insulation material having a thickness of 1 mm was prepared in the same manner as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with decyl(C10)dimethylamine ("FARMIN DM1098" manufactured by Kao Corporation, 0.5 parts by mass as the active ingredient).

[0284] (Example 23)

[0285] A heat insulating material having a thickness of 1 mm was prepared by the same method as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with tetradecyl (C14)amine acetate ("CATION MA" manufactured by NOF Corporation, 0.5 parts by mass as the active ingredient).

[0286] (Example 24)

[0287] A thermal insulation material having a thickness of 1 mm was produced in the same manner as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with octadecyl (C18)amine acetate ("CATION SA" manufactured by NOF Corporation, 0.5 parts by mass as the active ingredient).

[0288] (Example 25)

[0289] A thermal insulation material having a thickness of 1 mm was prepared in the same manner as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with octyl(C8)dimethylamine ("FARMIN DM0898" manufactured by Kao Corporation, 0.5 parts by mass as the active ingredient).

[0290] (Example 26)

[0291] A thermal insulation material having a thickness of 1 mm was prepared in the same manner as in Example 1 except that the dodecyltrimethylammonium chloride as the non-polymeric dispersant in Example 1 was replaced with stearylpropylene glycol (C21) dimethylamine ("CATINAL SHPA-80" manufactured by Toho Chemical Co., Ltd., 0.5 parts by mass as the active ingredient).

[0292] (Example 27)

[0293] Using the same type and amount of non-polymer dispersant as in Example 25, and using a floating oven (hot air dryer) and an IR oven, adjusting the drying conditions so that the presence rate of the non-polymer dispersant in the insulating material becomes 0.0003 mass %, an insulating material with a thickness of 1 mm was produced by the same method as in Example 1.

[0294] Next, the content of octyl dimethylamine contained in the obtained insulating material (insulating layer) is determined by liquid chromatography mass spectrometry (LC / MS). First, prepare standard solutions of various concentrations in which FARMIN DM0898 is dissolved, and make a standard curve of the concentration of octyl dimethylamine and the area value of LC / MS. Next, take 0.4g of insulating material, add it to 10mL of methanol and shake it for more than 1 hour, thereby extracting the octyl dimethylamine contained in the insulating material. The obtained solution is passed through a membrane filter (0.20μm) and put into LC / MS, and the content of octyl dimethylamine in the solution is determined according to the previous standard curve. The content of octyl dimethylamine contained in the insulating material is calculated according to the content of octyl dimethylamine contained in 0.4g of insulating material, and it can be seen that the result is 0.00029% by mass.

[0295] In addition, the conditions of LC / MS measurement are as follows.

[0296] Measuring apparatus: High performance liquid chromatography-mass spectrometer (manufactured by Thermo Fisher Scientific, UltiMate 3000 / TSQ QUANTUMACCESS MAX).

[0297] Chromatographic column: "L-column3 C18" manufactured by the Institute for Evaluation of Chemical Substances.

[0298] The eluent composition was pure water (with ammonium acetate added) / methanol gradient conditions.

[0299] Flow rate: 0.6mL / min.

[0300] Detector: MS (full scan: 100-500, m / z=158).

[0301] Column temperature: 40℃.

[0302] Injection volume: 5 μL.

[0303] Ionization method: ESI (POS.).

[0304] Ion spray voltage: 3.0 kV.

[0305] Evaporation temperature: 350℃.

[0306] Capillary temperature: 270°C.

[0307] <Determination of initial cone penetration of mixed liquid>

[0308] For each mixed solution obtained in Examples 1 to 27 and Comparative Examples 1 to 5, the cone penetration was measured according to the "non-working cone penetration" in accordance with the contents described in Japanese Industrial Standard JIS K2220: 2013 "Grease-Part VII: Cone Penetration Test Method". Specifically, a crucible of a size that does not contact the weight of the cone when the weight is lowered is prepared, the mixed solution is filled therein, and it is arranged on a PENETRO METER made by Nikka-engineering equipped with a weight. Next, the position of the weight is adjusted to the position where the weight contacts the mixed solution, and this position is set to 0 point. Then, at room temperature (25°C), the weight is lowered for 5 seconds (±0.1 seconds), and the depth (mm)×10 of the weight that falls into the mixed solution is calculated as the cone penetration. It should be noted that the cone weight is a standard cone specified in the Japanese Industrial Standard, a weight with a total mass of 102.5g is used, and a weight with a mass of 47.5g±0.05g is used as the weight of the weight holder. Tables 1, 2, and 3 show the results of cone penetration of the obtained mixed solutions.

[0309] <Evaluation of dispersion stability of mixed solution (change rate of cone penetration after the mixed solution was left to stand for 24 hours)>

[0310] Each mixed solution obtained in Examples 1 to 27 and Comparative Examples 1 to 5 was allowed to stand for 24 hours, and the cone penetration after standing was measured by the same method as the "Initial cone penetration measurement of the mixed solution". Then, the obtained cone penetration value was substituted into the following formula: {(initial cone penetration of the mixed solution) - (cone penetration of the mixed solution after standing for 24 hours)} / (initial cone penetration of the mixed solution) × 100 [%], and the change rate of the cone penetration of the mixed solution after standing for 24 hours was calculated to evaluate the dispersion stability of the mixed solution. The dispersion stability (change rate of cone penetration) of the obtained mixed solution is shown in Table 1, Table 2 and Table 3.

[0311] <Measurement of compression deformation rate of thermal insulation material (insulation layer)>

[0312] The compression set rate of each thermal insulating material (thermal insulating layer) obtained in Examples 1 to 27 and Comparative Examples 1 to 5 was measured by the following method.

[0313] A precision universal testing machine (Autograph AGS-5kNX, manufactured by Shimadzu Corporation) was used to perform a compression test of the thermal insulation material at a compression speed of 0.5 mm / min, and the compression strain [%] (compression displacement / initial thickness of the test body) and the compression stress [MPa] were measured. Then, the compression strain when the compression stress reached 2 MPa was read and used as the compression deformation rate of the thermal insulation material. The compression deformation rates of the obtained thermal insulation materials are shown in Tables 1, 2, and 3.

[0314] <Measurement of thermal conductivity of thermal insulation materials (insulation layers)>

[0315] The thermal conductivity of each thermal insulating material (thermal insulating layer) obtained in Examples 1 to 27 and Comparative Examples 1 to 5 was measured by the following method.

[0316] For thermal conductivity, two measurements were performed at 80°C and 2 MPa and at 600°C and 2 MPa, respectively, in accordance with the contents of Japanese Industrial Standard JIS A 1412-2:1999 "Determination of thermal resistance and thermal conductivity of thermal insulating materials - Part 2: Heat flow meter method (HFM method)". First, the thermal insulation material (thickness 1 mm when not pressurized) was cut into a size of 20 mm × 20 mm to prepare a sample. Prepare a sample, a reference sample (alumina composite material ("RS-100", manufactured by ZIRCAR Refractory Composites, Inc., thickness: 5 mm, thermal conductivity: 0.66 W / (m·K))), and a titanium plate (thickness 0.2 mm). Next, thermocouple 1 (sheathed thermocouple K type (SCHS1-0), φ=0.15, Class JIS1, manufactured by Chino), titanium plate, thermal insulation material as a test body, titanium plate, thermocouple 2 (sheathed thermocouple K type (SCHS1-0), φ=0.15, Class JIS1, manufactured by Chino), standard plate, thermocouple 3 (sheathed thermocouple K type (SCHS1-0), φ=0.15, Class JIS1, manufactured by Chino) are clamped in order from the top on the lower plate of the pneumatic press (manufactured by Imoto Seisakusho Co., Ltd.), and the thermal insulation material, standard plate, thermocouple, etc. are closely attached. Next, the upper plate and the lower plate are heated, and the load of the press is adjusted to 800N (equivalent to 2MPa), and then pressurized. In the heated and pressurized state, the measurement is continued until the detection temperature of the thermocouple is stabilized. It should be noted that, for the measurement temperature, two types of measurements were performed, one in which the upper plate was set at 80°C and the lower plate was set at 30°C, and the other in which the upper plate was set at 600°C and the lower plate was set at 40°C. In addition, temperature stability means that the temperature change after 10 minutes is within ±0.1°C. Based on the detection temperature of each thermocouple after temperature stabilization, the thickness of the thermal insulation material during compression, the thermal conductivity and thickness of the standard sample, the thermal conductivity k1 of the thermal insulation material is calculated by the following formula (I). The thermal conductivity of the obtained thermal insulation material is shown in Tables 1, 2 and 3.

[0317] k1=k2×(L1×ΔT1) / (L2×ΔT2)……(I)

[0318] (Wherein, k1 is the thermal conductivity of the insulation material [W / (m·K)], k2 is the thermal conductivity of the standard plate [W / (m·K)], L1 is the thickness of the insulation layer when pressurized, L2 is the thickness of the standard plate, ΔT1 is the temperature difference between the temperature of the second thermocouple and the temperature of the third thermocouple, and ΔT2 is the temperature difference between the temperature of the first thermocouple and the temperature of the second thermocouple.)

[0319] (Thermal resistance)

[0320] The thermal resistance of the thermal insulation material is calculated by the following formula (II) based on the thermal conductivity k1 and the thickness L1 when pressed.

[0321] R1=L1 / k1……(II)

[0322] (Where R1 is the thermal resistance of the insulation layer [(m 2 ·K) / W], k1 is the thermal conductivity of the insulation layer [W / (m·K)], and L1 is the thickness of the insulation layer when pressurized.

[0323] <Measurement of density of thermal insulation material (insulation layer)>

[0324] The density of each thermal insulating material (thermal insulating layer) obtained in Examples 1 to 27 and Comparative Examples 1 to 5 was measured by the following method.

[0325] Cut the insulation material into 20 mm × 20 mm pieces, measure the mass and thickness, divide the mass by the volume, and calculate the density [g / cm 3 ]. The densities of the obtained thermal insulation materials are shown in Tables 1, 2 and 3.

[0326] It should be noted that the upward arrows in Table 1, Table 2 and Table 3 indicate that the content of the cell filled with the arrow is the same as the content of the cell above it.

[0327] [Table 1]

[0328]

[0329] [Table 2]

[0330]

[0331] [Table 3]

[0332]

[0333] As shown in Tables 1, 2, and 3, when using a BET specific surface area of ​​90 m 2 / g or more and less than 380m 2 In Examples 1 to 17 and Examples 18 to 27, which contain at least one of the non-polymeric dispersants represented by the above formulas (A1), (A2), (A3) or (A4) of silica particles of 0.1 g / g, inorganic fibers, and the above formulas (A1), (A2), (A3) or (A4), the viscosity increase of the mixed solution is suppressed (the cone penetration value is high), and the productivity is excellent. On the other hand, the thermal conductivity of Comparative Example 1 in which the BET specific surface area of ​​the silica particles is too small is high. In addition, in Comparative Example 2 in which the BET specific surface area of ​​the silica particles is too large, and Comparative Examples 3 to 5 in which only a material that does not belong to any of the above formulas (A1) to (A4) is used as a dispersant, the mixed solution is significantly more viscous (low cone penetration) than in the examples.

[0334] <<Experimental Example 2>>

[0335] (Example 1B)

[0336] In Example 1, the coating thickness of the mixed solution was changed to 4 mm to obtain a thickness of 2 mm and a density of 0.3 to 0.5 g / cm 3 The sheet was compressed by a hot press. A heat insulating material (heat insulating layer) having a thickness of 2 mm was prepared in the same manner as in Example 1 except for the above.

[0337] (Examples 4B, 12B, 18B to 20B, 22B to 26B)

[0338] In each of Examples 4, 12, 18 to 20, and 22 to 26, the coating thickness of the mixed solution was changed to 4 mm to obtain a thickness of 2 mm and a density of 0.3 to 0.5 g / cm 3 The heat insulating materials (heat insulating layers) of Examples 4B, 12B, 18B to 20B, and 22B to 26B having a thickness of 2 mm were prepared in the same manner as in Example 1 except for the above.

[0339] For the obtained thermal insulation material (thermal insulation layer), both thermal conductivity measurements and density measurements were performed under the conditions of 80°C and 2MPa and 600°C and 2MPa in the same manner as in Experimental Example 1. As a result, in the measurement under the conditions of 80°C and 2MPa, the thermal conductivity of Example 1B was about the same as that of Example 1, and the same was true for Examples 4B, 12B, 18B to 20B, and 22B to 26B. On the other hand, in the measurement under the conditions of 600°C and 2MPa, different tendencies were observed regarding the influence of the thickness of the thermal insulation material on the thermal conductivity depending on whether other inorganic particles were contained. The results of the thermal conductivity measurements under the conditions of 600°C and 2MPa were compared for Examples 1B, 4B, 12B, 18B to 20B, 22B to 26B and the corresponding Examples 1, 4, 12, 18 to 20, and 22 to 26, and are shown in Table 4 together with the density of each thermal insulation material (thermal insulation layer).

[0340] [Table 4]

[0341] Table 4

[0342]

[0343] According to the results shown in Table 4, in Examples 18 to 20 and Examples 18B to 20B, which are insulating materials (insulating layers) formed by molding a mixture containing other inorganic particles (here, carbon-based particles), the values ​​of the thermal conductivity at 600°C and 2MPa do not substantially change regardless of whether the thickness is 1 mm or 2 mm, and the increase in thermal conductivity caused by the increase in thickness is suppressed compared to other examples. This is considered to be because in Examples 18 to 20 and Examples 18B to 20B, the presence of other inorganic particles suppresses heat radiation.

[0344] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the scope of the claims includes various modifications and changes to the specific examples described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0346] 1: Insulating material; 10, 10A, 10B, 521: Insulating layer; 20, 20A, 20B, 522: Buffer layer; 30, 523: Coating material (coating layer); 31A, 31B: Resin film; 32: Sealing part; 33: Vent; 34: Vent film; 40: Adhesive layer; 50: Battery module; 51: Single battery.

Claims

1. A thermal insulation material comprising a thermal insulation layer, wherein the thermal insulation layer contains silica particles, inorganic fibers, and at least one of the non-polymeric dispersants represented by the following formula (A1), (A2), (A3) or (A4), wherein the silica particles have a BET specific surface area of ​​90 m 2 / g or more and less than 380m 2 / g, In formula (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 1 , R 2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40, wherein R 1 , R 2 , R 3 and R 4 The hydrocarbon groups are optionally bonded to each other to form a ring structure, In formula (A3), R 5 represents a hydrocarbon group optionally containing a heteroatom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a heteroatom or a hydrogen atom, and R 5 , R 6 and R 7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40, wherein R 5 , R 6 and R 7 The hydrocarbon groups are optionally bonded to each other to form a ring structure, In formula (A4), R 8 and R 9 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40, wherein R 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

2. The thermal insulation material according to claim 1, wherein: The content of the non-polymeric dispersant in the heat insulating layer is 0.01% by mass to 5% by mass.

3. The thermal insulation material according to claim 1, wherein The silica particles are at least one selected from the group consisting of dry silica, wet silica, and silica aerogel.

4. The thermal insulation material according to claim 1, wherein The silica particles are at least one selected from the group consisting of hydrophilic fumed silica and hydrophobic fumed silica.

5. The thermal insulation material according to any one of claims 1 to 4, wherein The average primary particle size of the silica particles is 100 nm or less.

6. The thermal insulation material according to any one of claims 1 to 4, wherein The inorganic fiber is at least one selected from the group consisting of glass fibers and biosoluble inorganic fibers.

7. The thermal insulation material according to any one of claims 1 to 4, wherein The density of the thermal insulation layer is 0.2 g / cm 3 ~0.5g / cm 3 .

8. The thermal insulation material according to any one of claims 1 to 4, wherein The thermal conductivity of the thermal insulation layer under the conditions of 80° C. and 2 MPa pressure is 0.045 W / (m·K) or less.

9. The thermal insulation material according to any one of claims 1 to 4, wherein The thermal conductivity of the thermal insulation layer under the conditions of 600° C. and 2 MPa pressure is less than 0.08 W / (m·K).

10. The thermal insulation material according to any one of claims 1 to 4, wherein The thermal insulation material further includes a coating layer composed of a resin film, The heat insulating material is a stack of the heat insulating layer and the coating layer.

11. The thermal insulation material according to claim 10, wherein The thermal insulation material is laminated with two or more coating layers. The two or more covering layers sandwich and enclose the heat insulating layer in the thickness direction, thereby sealing the gaps between the covering layers.

12. The thermal insulation material according to claim 11, wherein The coating layer has a vent hole connecting the gap with an external space.

13. The thermal insulation material according to any one of claims 1 to 4, wherein The thermal insulation material is disposed between the single cells of the battery module.

14. A method for manufacturing a thermal insulation material, comprising: A mixing step of mixing silica particles, inorganic fibers, and a non-polymeric dispersant represented by the following formula (A1), (A2), (A3), or (A4) in a solvent to obtain a mixed solution; a coating step of coating the mixed solution obtained in the mixing step to obtain a coating film; and a molding step of molding the coating film obtained in the coating step to obtain a heat insulating layer, In formula (A1) and (A2), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 1 , R 2 , R 3 and R 4 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40, wherein R 1 , R 2 , R 3 and R 4 The hydrocarbon groups are optionally bonded to each other to form a ring structure, In formula (A3), R 5 represents a hydrocarbon group optionally containing a heteroatom, R 6 and R 7 Each independently represents a hydrocarbon group optionally containing a heteroatom or a hydrogen atom, and R 5 , R 6 and R 7 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40, wherein R 5 , R 6 and R 7 The hydrocarbon groups are optionally bonded to each other to form a ring structure, In formula (A4), R 8 and R 9 Each independently represents a hydrocarbon group optionally containing a heteroatom, and R 8 and R 9 The total number of carbon atoms obtained by combining the hydrocarbon groups is 8 to 40, wherein R 8 and R 9 The hydrocarbon groups are optionally bonded to each other to form a ring structure.

15. The method for producing a thermal insulation material according to claim 14, wherein: The amount of the non-polymeric dispersant added to the mixed solution is 0.05 to 5 parts by mass based on 100 parts by mass of the silica particles.

16. The method for producing a thermal insulation material according to claim 14 or 15, wherein: The solvent is a protic solvent.

17. The method for producing a thermal insulation material according to claim 14 or 15, wherein: The surface tension of the solvent is less than 73 mN / m.

Citation Information

Patent Citations

  • Heat insulation sheet for battery pack and battery pack

    JP2021034278A

  • Connector

    JP2022131070A